Aqueous carbon nanotube dispersions, pastes, cathodes and anodes

JP2024545797A5Pending Publication Date: 2025-04-04MCD TECHNOLOGIES S A RL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024540545
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-29
Filing Date
2022-05-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing carbon nanotube dispersions for lithium ion battery electrodes face challenges with high viscosity during storage and application, leading to instability and non-uniform mixing, which affects the quality and performance of the electrodes.

Method used

Aqueous dispersions of single-walled and double-walled carbon nanotubes stabilized by a gelling agent, forming a weak gel network that maintains high viscosity during storage and low viscosity during processing, achieved through a specific weight ratio and rheological properties.

Benefits of technology

The dispersions provide stable electrode slurries with high viscosity during storage and low viscosity during application, ensuring uniform mixing and improved battery performance with increased capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention proposes a dispersion containing water, a gelling agent and 0.3-2 wt. % single-walled and / or double-walled carbon nanotubes, with a mass ratio of single-walled and / or double-walled carbon nanotubes to gelling agent of ≧0.05 and ≦10, containing gel particles formed by agglomerates of molecules of the gelling agent and physically linked by the single-walled and / or double-walled nanotubes into a weak gel network. Also proposed are methods for preparing the dispersion, methods for preparing the cathode and anode pastes, the cathode and anode pastes, and the cathodes and anodes. The present invention solves the problem of producing aqueous dispersions of single-walled and / or double-walled carbon nanotubes that exhibit both high stability during storage and transportation and low viscosity during the various manufacturing processes used, such as in the preparation of electrode pastes and subsequent electrodes for lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to aqueous dispersions of single-walled and / or double-walled carbon nanotubes and aggregates thereof, which dispersions have both high stability and moderate viscosity. The present invention also relates to a method for their preparation. The present invention also relates to the use of such dispersions for preparing electrode slurries. The present invention also relates to electrode slurries. The present invention also relates to lithium ion battery electrodes and methods for preparing lithium ion battery electrodes. [Background technology]

[0002] Dispersions of single-walled and double-walled carbon nanotubes can be used to incorporate carbon nanomaterials into a variety of coatings and composites, including electrode slurries for producing lithium-ion battery electrodes.

[0003] The use of single-walled and / or double-walled carbon nanotubes in lithium-ion battery cathodes and electrodes can increase the capacity of the electrodes and the entire battery, reduce their internal resistance, and extend the charge-discharge cycle life of lithium-ion battery electrodes, particularly silicon-containing anodes of lithium-ion batteries, as demonstrated, for example, by Russian Patent No. 2749904.

[0004] Single-walled and double-walled carbon nanotubes tend to bundle and aggregate into more complicated shapes. Although the aggregation of carbon nanotubes into long and thick bundles is desirable in some embodiments, including to ensure high electrical conductivity of the electrode, it leads to a faster settling rate of the dispersed carbon nanotube aggregates, i.e., a lower stability of the dispersion and / or electrode slurry. A lower stability of the dispersion leads to a shorter storage time of the dispersion, restricting potential logistics and process capabilities, and increasing the risk of non-uniform subsequent mixing with electrode slurry materials, resulting in an increased risk of rejects in lithium-ion battery manufacturing. These risks are associated to a greater extent with the lower stability of the electrode slurry containing single-walled and / or double-walled carbon nanotubes and their aggregates.

[0005] Methods for improving the stability of dispersions by preventing the aggregation of dispersed particles such as carbon nanotubes through the use of dispersants and surfactants are known in the art. In the case of single-walled carbon nanotubes, chlorosulfonic acid, for example, is known to completely shift the equilibrium of the aggregation process towards individual nanotubes [ANG Parra-Vasquez, N. Behabtu, MJ Green, CL Pint, CC Young, J. Schmidt, E. Kesselman, A. Goyal, PM Ajayan, Y. Cohen, Y. Talmon, RH Hauge, M. Pasquali, Spontaneous Dissolution of Ultralong Single-and Multiwalled Carbon Nanotubes, ACS Nano 2010 4(7), 3969-3978]. However, this approach has the drawback that the long bundles of carbon nanotubes are reduced or eliminated in the dispersion, although their presence is advantageous in some embodiments since it reduces the electrical percolation threshold and increases the electrical conductivity of coatings or composites (e.g., lithium ion battery electrodes) obtained using this type of dispersion.

[0006] On the other hand, dispersions of single- or double-walled carbon nanotubes are characterized by high viscosity, which grows with increasing concentration of nanotubes and bundles and their aspect ratios [ANG Parra-Vasquez, JG Duque, MJ Green, M. Pasquali, Assessment of length and bundle distribution of dilute single-walled carbon nanotubes by viscosity measurements, AIChE J., 60 (2014) 1499-1508]. Further aggregation of carbon nanotube bundles into complex shaped aggregates leads to very high viscosity of the dispersion, making further utilization of the dispersion technically difficult, for example for coating or transport through process lines in manufacturing processes.

[0007] At the same time, high viscosity of the dispersion reduces the mobility of the carbon nanotubes and their bundles and the settling rate of the aggregates, thus improving the stability of the dispersion. Conversely, the mobility and settling rate of the aggregates are higher in low viscosity dispersions. Thus, the selection of a carbon nanotube dispersion involves finding a middle ground between high stability and low viscosity of the dispersion.

[0008] Thus, the technical problem is to obtain a dispersion, including the production of electrode slurries for lithium-ion batteries, in which high stability of the dispersion and the opportunity for long-term storage without stratification and property changes are combined with the low viscosity required for the use of the dispersion. A similar technical problem exists for electrode slurries containing single-walled and / or double-walled carbon nanotubes, which require the provision of high viscosity during storage before use (application to the current collector of the electrode), high viscosity after application to the current collector without spreading to ensure good quality of the edges of the active material layer of the electrode, and at the same time low viscosity of the electrode slurry under defined processing conditions for application to the current collector.

[0009] There are solutions to obtain a highly viscous gel containing carbon nanotubes in a dispersed state. WO2006112162 provides a gel containing dispersed carbon nanotubes based on an ionic liquid, such as obtained by a neutralization reaction of benzoic acid or its derivatives and a base. This gel containing carbon nanotubes ensures unlimited long-term storage without aggregation of the nanotubes and settling of these aggregates. However, the use of ionic liquids as dispersion liquids greatly limits the applications of the dispersion. For most applications, including the production of electrode slurries, such gels cannot be used directly, but a dispersion based on aqueous and / or organic solvents containing mainly neutral molecules must be obtained therefrom before use. The stability of this dispersion is no longer guaranteed by the stability of the initial gel, nor that of the electrode slurry. Moreover, in many embodiments, including the production of electrode slurries and lithium-ion battery electrodes, the initial component of the ionic liquid may be undesirable even after dilution and dispersion in a solvent.

[0010] Some known solutions provide dispersion compositions in which the viscosity of the dispersion and / or its complex modulus is in a narrow range, intermediate between the high viscosity necessary to keep the good quality of the carbon nanotube dispersion and the low viscosity desired for good workability of pumping the dispersion and converting it into the final product. For example, EP 3333946 claims a dispersion of carbon nanotube bundles in a dispersion medium, which also contains 1-15% by weight of hydrogenated nitrile butadiene rubber obtained by hydrogenation of conjugated dienes, the dispersion further characterized by a complex modulus of 20-500 Pa at 1 Hz. The inventors of the cited patent use the complex modulus at 1 Hz as some general rheological characteristics of liquids: at a low complex modulus the liquid viscosity is too low; if the complex modulus is high and the process (electrode formation) is no longer viable, the liquid viscosity is too high. As described in the cited patent, the viscosity of the dispersions with the above complex modulus is between 2 and 20 Pa·s at a shear rate of 1 / (6.3 s). EP 3333946 does not aim to ensure high stability of the dispersion. However, limiting the viscosity to less than 20 Pa·s is not sufficient for the dispersion to remain stable for long periods, a drawback that prevents an efficient manufacturing process, including good storage and transportation of the dispersion.

[0011] Japanese Patent No. 6860740 describes the viscosity of the dispersion and / or its complex modulus G*=(G' 2 +G'' 2 ) 1 / 2and at the same time limiting the phase angle, i.e., the arctangent of the ratio between the loss modulus G'' and the storage modulus G' measured by applying a shear strain oscillating at a frequency of 1 Hz. This publication claims a dispersion containing carbon nanotubes, carboxymethylcellulose or a salt thereof, and water, in which the weighted average molecular weight of the carboxymethylcellulose or a salt thereof is 10,000 to 100,000, the degree of esterification is 0.5 to 0.9, and the product (X×Y) of the complex modulus X (Pa) and the phase angle Y (°) of the dispersion is 100 to 1500. This means that the suspension of the present invention satisfies condition (1), where G'' is the loss modulus and G' is the storage modulus (measured by applying a shear strain oscillating at a frequency of 1 Hz). JPEG2024545797000002.jpg12156

[0012] A simple mathematical analysis of condition (1) shows that it does not limit the storage modulus G', which determines the elastic properties of the dispersion. The value limited by the invention is a monotonic function of the loss modulus G''. Condition (1) limits the loss modulus, which determines the viscous properties of the dispersion, and should be G'' < 26.18 Pa at high values ​​of G' → ∞ and even smaller at limited values ​​of the storage modulus. At the same time, condition (1) limits the phase angle, which should be less than 3 to 7.5 degrees to fulfill this condition at just moderate values ​​of the complex modulus of 200 to 500 Pa. Such values ​​of the phase angle are typical in rigid gels. Patent publication 6860740 thus provides a rigid gel of a low-viscosity dispersion. The drawback of this solution is very obvious: the destruction of such a gel produces large aggregates, several tens of micrometers in size, which cannot be destroyed further due to the low viscosity of the dispersion and therefore the low shear stress. Therefore, mixing the dispersion with the active components of the electrode slurry makes it difficult to produce a uniform slurry, whose rheological properties are not optimal, for example, the slurry viscosity may be too low to ensure its stability. Another embodiment of the invention described in Japanese Patent No. 6860740 provides, with the above limitations, a dispersion characterized by a phase angle of more than 15 degrees but a complex modulus of less than 50 Pa, which means a very low viscosity of the dispersion and therefore its low stability.

[0013] Japanese Patent No. 6860740 is used as the prototype for this application.

[0014] There is therefore a technical problem of obtaining an aqueous dispersion of single-walled and / or double-walled carbon nanotubes that has both high stability during storage and transportation and low viscosity under the various processes of its use, including the manufacture of an electrode slurry and then a lithium-ion battery electrode. There is a similar technical problem for electrode slurries containing single-walled and / or double-walled carbon nanotubes, which must provide high viscosity during storage before use (application to the current collector of the electrode), high viscosity after application to the current collector without spreading to ensure good quality of the edges of the active material layer of the electrode, and at the same time low viscosity of the electrode slurry under defined processing conditions for application to the current collector. As a result, there is a problem of producing high quality lithium-ion battery electrodes, demonstrated by high specific capacity and stable operation in successive charge-discharge cycles. Known solutions, including those in JP 6860740 adopted as a prototype, do not allow to solve this technical problem. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Russian Patent No. 2749904 [Patent Document 2] International Publication No. 2006112162 [Patent Document 3] European Patent No. 3333946 [Patent Document 4] Patent No. 6860740 [Non-patent literature]

[0016] [Non-Patent Document 1] ANGParra-Vasquez, N. Behabtu, MJGreen, CLPint, CC Young, J. Schmidt, E. Kesselman, A. Goyal, PMAjayan, Y. Cohen, Y. Talmon, RH Hauge, M. Pasquali, Spontaneous Dissolution of Ultralong Single-and Multiwalled Carbon Nanotubes, ACS Nano 2010 4(7), 3969-3978 [Non-Patent Document 2] ANGParra-Vasquez, JGDuque, MJGreen, M.Pasquali,Assessment of length and bundle distribution of dilute single-walled carbon nanotubes by viscosity measurements,AIChE J.,60(2014)1499-1508 Summary of the Invention

[0017] In order to solve the technical problem, the dynamic viscosity of the dispersion at rest during storage is 1 / 6.3s -1 20 Pa·s at shear rates below 18.6 Pa·s, allowing the dispersion to be stored and / or transported for long periods without aggregation and / or settling of the carbon nanotubes, and the dynamic viscosity of the dispersion in the process stream is significantly lower, i.e., 18.6 s -1 The viscosity of the dispersion is preferably less than 2 Pa·s at shear rates of 1 / 6.3 s or more, i.e. sufficiently low for the processing in which the dispersion is used, including the electrode slurry manufacturing process. Hereinafter, the term "viscosity" refers to the kinematic viscosity at a temperature of 25°C. Storage and application conditions of the dispersion may be characterized by different temperatures which does not negate the advantages of the dispersion of the present invention. Importantly, the typical shear rates during storage and transportation given here and used below (<1 / 6.3 s) are also important. -1 ) and shear rate during processing (>18.6s -1 ) is not absolute and is considered a convention for the quantitative description of dispersion viscosity. The shear rate is 1 / 6.3s for some transport conditions.-1 In some processes using dispersions, the -1 This does not negate the advantages of the dispersion of the present invention. Research carried out by the inventors of the present application has shown that it is possible to produce dispersions of single-walled and / or double-walled carbon nanotubes and their aggregates that are non-ideal pseudoplastic fluids and that follow the Ostwald-de Waele power law known for some non-ideal liquids, see W. Ostwald, Ueber die rechnerische Darstellung des Strukturgebietes der Viskositat, Kolloid-Zeitschrift 47 (1929) 176-187: JPEG2024545797000003.jpg18156

[0018] This law suggests that their viscosity depends on the shear rate during liquid flow, i.e. the lower the viscosity, the higher the shear rate. Pseudoplastic fluids are characterized by n<1. The lower the flow behavior index n, the more pronounced the dependence of pseudoplastic fluid viscosity on shear rate. Further studies have shown that the flow behavior index can be significantly reduced by adding a gelling agent to a dispersion of single-walled and / or double-walled carbon nanotubes such that gel particles (domains) accumulate in the dispersion and are formed by the molecules of this gelling agent, which bind to single-walled and / or double-walled carbon nanotubes or aggregates containing carbon nanotubes with each other. This simultaneous introduction of the gelling agent and the single-walled and / or double-walled carbon nanotubes results in a synergistic effect that results in a lower flow behavior index n (i.e. a larger difference between the dispersion and an ideal Newtonian fluid) compared to the flow behavior index of the corresponding (comparable concentration) dispersion of carbon nanotubes in a solvent and gelling agent in a solvent.

[0019] The synergistic effect is caused by the presence in the dispersion of gel particles formed by aggregates of gelator molecules and physically linked by single- and / or double-walled carbon nanotubes into a weak gel network (some publications refer to weak gels as structured liquids). The resulting network provides a very high dispersion viscosity at low shear loads. However, the intermolecular bonds between the carbon nanotubes and the gelator molecules are weak enough, so that higher shear loads destroy them, resulting in lower viscosities. The resulting system can be characterized as a multicomponent (two-component) supramolecular gel (see review by E.R.Draper and D.J.Adams, How should multicomponent supramolecular gels be characterised? Chem.Soc.Rev.,2018,47,3395;doi:10.1039 / c7cs00804j) with one strong gelator and one weak gelator, the latter being a single- or double-walled carbon nanotube.

[0020] Having both single-walled and / or double-walled carbon nanotubes and gelling agent in suspension is not sufficient for said synergistic effect. If nanotubes and gelling agent are mixed and dispersed in water, and gelling agent and nanotubes form only a gel network of co-assembled gels, or conversely, gelling agent and nanotubes form two independent interpenetrating gel networks, the resulting gel does not have the problematic features in either case, and its properties are close to the prototype described above. However, if nanotubes and gelling agent are mixed and dispersed in water, and gelling agent particles (domains) in the solvent accumulate, providing conditions where single-walled and / or double-walled carbon nanotubes combine the gel domains containing only or mainly gelling agent into a single network of a two-component gel, the resulting dispersion shows a sharp viscosity as a function of shear rate, as described above, with a very low value of the flow behavior index.

[0021] Characterization of the gel structure: whether it consists only of bound aggregates (co-assembled gels) or contains single-component gel domains of gelators (or aggregates containing carbon nanotubes) linked by carbon nanotubes (self-sorted gels), requires special and non-standard research methods such as cryogenic transmission electron microscopy and NMR microtomography. On the other hand, the gel structure can be defined by its rheological properties, i.e. the viscosity as a function of the shear rate, or the complex modulus G* and its components G' and G'' as a function of the shear strain.

[0022] In one embodiment, the present invention provides a dispersion comprising water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, wherein the content of single-walled and / or double-walled carbon nanotubes is in the range of 0.3-2 wt %, the weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent is at least 0.05 and not more than 10, and the dispersion contains gel particles formed by aggregates of gelling agent molecules physically bound into a weak gel network by the single-walled and / or double-walled carbon nanotubes.

[0023] The present invention also provides, in one embodiment, a dispersion containing water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, the content of single-walled and / or double-walled carbon nanotubes being in the range of 0.3-2 wt %, the weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent being at least 0.05 and not more than 10, and the dispersion having a flow behavior index n of 0.37 or less and a flow behavior index of at least 3.2 Pa s n It is characterized as a pseudoplastic fluid having a flow consistency index K of

[0024] The dispersion having this composition, structure, or rheological properties may be dissolved at low shear rates (e.g., 1 / 6.3 s) due to the synergistic effect on the viscosity of the single-walled and / or double-walled carbon nanotubes and the gelling agent. -1 The very high dynamic viscosity of the dispersion at shear rates typical for processing (e.g., 18.6 s -1 It provides the benefit of low kinematic viscosity at temperatures above 200°C.

[0025] A gelling agent refers to a substance having polymer chains capable of forming net crosslinks by intermolecular forces (van der Waals forces, hydrogen bonds, etc.). This ensures a high viscosity of the dispersion at rest. However, high shear rates significantly reduce the viscosity of dispersions containing gelling agents. A polymer capable of intermolecular interactions can be a gelling agent. Examples of substances that can be used as gelling agents are, but are not limited to, carboxymethylcellulose and / or its salts, polyvinylpyrrolidone, polyvinylidene fluoride, hydrogenated nitrile butadiene rubber, polyacrylic acid and / or its salts, or mixtures thereof. Most preferably, the gelling agent is one of the following in the aqueous dispersion of the present invention: carboxymethylcellulose Na salt, carboxymethylcellulose Li salt, polyacrylic acid Na salt or polyacrylic acid Li salt, or polyvinylpyrrolidone. In some cases, two or more different gelling agents are present in the dispersion, preferably with single-walled and / or double-walled carbon nanotubes.

[0026] The gelling agent in the dispersion ensures a higher flow consistency index K and a lower flow behavior index n. The single-walled and / or double-walled carbon nanotubes and / or their aggregates in the dispersion also ensure a higher flow consistency index K and a lower flow behavior index n. Having both gelling agent and single-walled and / or double-walled carbon nanotubes and / or their aggregates in the dispersion, such that the dispersion contains gel particles formed by aggregates of gelling agent molecules physically bound to a weak gel network by single-walled and / or double-walled carbon nanotubes, creates a synergistic effect, resulting in a significantly lower flow behavior index n (i.e., a larger difference between the dispersion and an ideal Newtonian fluid) compared to the flow behavior index of the corresponding dispersion of carbon nanotubes in a solvent and gelling agent in a solvent. It also gives a higher loss modulus G'' and a higher phase angle δ=arctan(G'' / G') under oscillatory shear loading.

[0027] The preferred weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the dispersion is at least 0.1 and not more than 5. The most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the dispersion is at least 0.33 and not more than 3. However, synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the dispersion ranging from 0.05 to 0.33. In some embodiments, the most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the dispersion is at least 0.5 and not more than 2. Synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the dispersion ranging from 2 to 10.

[0028] Having single-walled and / or double-walled (but not multi-walled) carbon nanotubes in the dispersion is generally a prerequisite for the technical result. Single-walled carbon nanotubes are known to have small diameters of less than 4 nm, for example 1.5 nm, for stable single-walled carbon nanotubes, and at the same time large lengths that can exceed 5 μm. Single-walled carbon nanotubes therefore have a very large length-to-diameter ratio that can exceed 3000. Double-walled carbon nanotubes are also known to have an outer diameter not exceeding 6 nm (which can be, for example, 2.8 nm), and their length can also exceed 5 μm. This high length-to-diameter ratio gives the single-walled carbon nanotubes a significant impact on the dispersion rheology, which, combined with the synergistic effect of the simultaneous presence of a gelling agent, leads to the desired technical result. The aggregation of single-walled and / or double-walled carbon nanotubes can form aggregates with a length-to-diameter ratio that is somewhat smaller or larger than the length-to-diameter ratio of the individual nanotubes contained therein. The single-walled and / or double-walled carbon nanotube aggregates preferably contain bundles of single-walled and / or double-walled carbon nanotubes having a length-to-diameter ratio of greater than 100, more preferably a length-to-diameter ratio of single-walled and / or double-walled carbon nanotubes of greater than 500, and most preferably a length-to-diameter ratio of single-walled and / or double-walled carbon nanotubes of greater than 1000.

[0029] The content of single-walled and / or double-walled carbon nanotubes in the dispersion that allows the desired technical result to be achieved is 0.3-2 wt.%. The preferred content of single-walled and / or double-walled carbon nanotubes in the dispersion is determined by the process equipment used and the logistic characteristics. Preferably, the content of single-walled and / or double-walled carbon nanotubes is 0.3-1.4 wt.%. In some embodiments, the content of single-walled and / or double-walled carbon nanotubes is preferably 0.3-0.6 wt.%, most preferably 0.35-0.45 wt.%. In some other embodiments, the content of single-walled and / or double-walled carbon nanotubes in the dispersion is preferably 0.6-1.2 wt.%, most preferably 0.7-1 wt.%.

[0030] The ability of single-walled and / or double-walled carbon nanotubes to interact and aggregate (bundle) with each other via van der Waals forces (π-π interactions) is also very important to achieve technical results. Defects in single-walled and / or double-walled carbon nanotubes reduce this ability. Therefore, single-walled and / or double-walled carbon nanotubes preferably contain as few defects as possible. A quantitative indicator of the number of defects in the structure of single-walled and / or double-walled carbon nanotubes is the ratio of G and D line intensities in the Raman spectrum; the higher this ratio, the less defects the carbon nanotubes have. The preferred G and D line intensity ratio in the Raman spectrum at 532 nm is at least 10, the more preferred G and D line intensity ratio in the Raman spectrum at 532 nm is at least 40, the even more preferred G and D line intensity ratio in the Raman spectrum at 532 nm is at least 60, and the most preferred ratio is at least 80.

[0031] In addition to single-walled and / or double-walled carbon nanotubes, the dispersion may contain impurities of other carbon allotropes, including, but not limited to, amorphous carbon and / or graphite and / or multi-walled carbon nanotubes. The effect of these impurities on the dispersion rheology is minor and therefore the impurities do not affect the technical results.

[0032] The dispersion of single-walled and / or double-walled carbon nanotubes and / or agglomerates thereof may contain impurities of metals of groups 8 to 11 of the periodic table of elements, or metal carbides, such as iron or cobalt, used as catalysts in the production of carbon nanotubes, or other metals, bimetallic particles, or alloys thereof, which result from the method by which these carbon nanotubes are obtained. In some embodiments, including the production of an electrode slurry and further production of an electrode, the content of metal impurities of groups 8 to 11 of the periodic table of elements in the single-walled and / or double-walled carbon nanotubes and / or agglomerates thereof is preferably less than 1 wt. %. In some embodiments, the content of metal impurities of groups 8 to 11 of the periodic table of elements in the single-walled and / or double-walled carbon nanotubes and / or agglomerates thereof is more preferably less than 0.1 wt. %. In other embodiments, on the contrary, there is no reason to so limit the content of metal impurities of groups 8 to 11 of the periodic table of elements in the single-walled and / or double-walled carbon nanotubes and / or agglomerates thereof, so that it can be up to 15 wt. %.

[0033] For the best synergistic effect to achieve the minimum flow behavior index n, the surface of the single-walled and / or double-walled carbon nanotubes preferably contains functional groups such as, but not limited to, oxygen-containing groups (most preferably, the surface contains carboxyl and / or carbonyl and / or hydroxyl groups) or chlorine-containing groups. In this case, the interaction between the carbon nanotubes and the gelling agent molecules is stronger and the synergistic effect of the gelling agent and the nanotubes on the reduction of the flow behavior index is most pronounced. The functional groups can be generated on the surface of the carbon nanotubes by various methods known in the art. For example, carboxyl functional groups can be generated on the surface of the carbon nanotubes by heat treatment in a nitric acid solution, and chlorine-containing functional groups can be generated by one of the methods described in Russian Patent No. 2717516, but are not limited to the given examples. The functionalization methods, i.e., methods for generating functional groups on the surface of the carbon nanotubes, are outside the scope of this disclosure but can be found in the literature. The content of functional groups on the surface of the single-walled and / or double-walled carbon nanotubes is preferably at least 0.1% by weight; most preferably, the chlorine content on the surface of the single-walled and / or double-walled carbon nanotubes is at least 0.1% by weight. This technical result can also be achieved with single-walled and / or double-walled carbon nanotubes having a surface functionalized with at least 0.1% by weight of carbonyl and / or hydroxyl and / or carboxyl groups. However, the technical result can also be achieved with single-walled and / or double-walled carbon nanotubes that do not contain functional groups on the surface, for example, that have been intentionally heated in an inert atmosphere to remove potential functional groups on the surface.

[0034] Dispersions containing water, a gelling agent and single-walled and / or double-walled carbon nanotubes are pseudoplastic and exhibit a very strong dependence of the dispersion viscosity on the shear rate in the flow due to the synergistic interaction of the single-walled and / or double-walled carbon nanotubes and the gelling agent in the dispersion. This solves for most embodiments the technical problem of, on the one hand, providing a high viscosity dispersion at rest (during storage and / or transportation) and, on the other hand, providing the required viscosity under certain dispersion use conditions when the dispersion flows through a pipe or is sprayed through a nozzle or in other applications with a given shear rate in the flow. To solve this problem, the flow behavior index n is preferably sufficiently small, not more than 0.37, and the flow consistency index K is at least 3.2 Pa·s n More preferably, the flow behavior index n is less than or equal to 0.30. Most preferably, the flow behavior index n is less than or equal to 0.2.

[0035] The flow behavior index n and the flow consistency index K are the dispersion viscosity μ as a function of shear rate γ, as described by the Ostwald-de Waele power equation (2): eff It is important to note that the dispersion viscosity as a function of shear rate may not follow the Ostwald-de Waele power law exactly. If the dispersion viscosity as a function of shear rate is different from the power law, the flow behavior index n and the flow consistency index K are taken as the parameters that correspond to the best linear approximation on the plot of the logarithm of viscosity as a function of the logarithm of shear rate, for example based on the least squares criterion.

[0036] The flow behavior index n and the flow consistency index K preferably satisfy the following condition: n<1.25 lg(K / (Pa s n ))-0.628. In this case, the viscosity of the dispersion at rest during storage is 1 / 6.3s -1 The shear rate remains high at above 20 Pa·s at shear rates below 20 Pa·s, allowing long-term storage and / or transportation of the dispersion without aggregation and / or settling of the carbon nanotubes and their aggregates.

[0037] The flow behavior index n and the flow consistency index K preferably satisfy the following conditions: n<1.24-0.787 . lg(K / (Pa·s n In this case, the dispersion viscosity in the flow is 18.6s -1 at shear rates above 2 Pa s and therefore sufficiently low to process this dispersion, including for the preparation of electrode slurries.

[0038] The dispersion is preferably characterized by a loss modulus of at least 27 Pa when subjected to oscillatory shear strain at a frequency of 1 Hz and a relative shear strain amplitude of 1%. The loss modulus G'' can be measured using a rotational rheometer equipped with a cone-and-plate cell or a plate-and-plate cell. In a plate-and-plate cell, since the length of the single-walled carbon nanotube bundles can be several tens of μm, it is important that the gap between the plates is at least 500 μm in order to measure the loss modulus accurately. If the gap is set smaller, wall effects can become large, which can lead to erroneous measurements.

[0039] In one embodiment, the present invention provides a method for producing a dispersion containing water, a gelling agent, and 0.3-2 wt. % single-walled and / or double-walled carbon nanotubes, the weight ratio of the single-walled and / or double-walled carbon nanotubes to the gelling agent being at least 0.05 and not more than 10, the method comprising alternating a series of at least three dispersion stages (D) and at least two rest stages (R), each of which is a dispersion stage (D) lasting at least 10,000 s -1 or ultrasonicating the dispersion at a frequency of at least 20 kHz with a specific input energy of at least 1 W h / kg, wherein the resting phase (R) is a phase in which the dispersion between two successive dispersion phases (D) is stirred for at least 1 min for 10 s -1 The method is characterized by exposure to a shear rate of less than 100 nm.

[0040] The provided method for the preparation of the dispersion allows, on the one hand, to disperse the single-walled carbon nanotubes due to the high shear rates in stage (D) and, on the other hand, to form, in the rest stage (R), a separated structure of a two-component gel containing gel domains with gelling agent mainly linked in a single network by single-walled and / or double-walled carbon nanotubes or agglomerates containing single-walled and / or double-walled carbon nanotubes. It should be noted that this preparation method ensures a better dispersion and distribution of the single-walled and / or double-walled carbon nanotubes. Since the obtained dispersion is pseudoplastic, during the mechanical processing or ultrasonic treatment, local low-viscosity zones in areas with high shear rates and local high-viscosity zones in areas with low shear rates may be formed, with low or almost no mass transfer between these zones. For this reason, the provided method allows the technical result to be achieved by repeating the mechanical processing or ultrasonic treatment stages more than twice, the dispersion being at rest for at least 1 minute between the cyclically repeated stages of mechanical processing or ultrasonic treatment or being at rest for at least 10 s. -1 This suggests that the shear rate must be relatively low, less than 100 s.

[0041] Mechanical processing can be carried out using a variety of dispersing or mixing equipment that provides the desired shear rate in the dispersion stream, including, for example, rotor-stator dispersers and homogenizers (dissolvers), colloid mills, bead mills, planetary mills, high pressure homogenizers (HPH), and rotary pulsating apparatus (RPA). In some embodiments, disk dissolvers, i.e., vertical agitators with disk impellers (preferably with toothed disk impellers), are sufficient for mechanical activation and are preferred. When using a bead mill or high pressure homogenizer with the dispersion stream passing through a very high shear rate zone, the dispersion stage (D) includes forcing the entire volume of the dispersion into the mill or homogenizer. In this case, the stationary stage (R) includes the step of forcing the entire volume of the dispersion, including the solvent, HNBR, and single-walled and / or double-walled carbon nanotubes, into the tank during the dispersion cycle and dispersing the mixture for 10 s. -1 This means that the mixture is only slowly stirred at a shear rate less than 100 rpm.

[0042] The choice of equipment for mechanical or ultrasonic processing, the specific power, the duration of the treatment at each stage depends on the available equipment and the composition of the dispersion, i.e. the selected solvent, the concentration of carbon nanotubes, the concentration and grade of selected HNBR, and the availability of other fillers and additives. In this regard, some equipment options may not apply to some dispersion compositions.

[0043] In some cases, the method preferably includes a series of at least five dispersion stages (D) alternating with at least four stationary stages (R), any one of the dispersion stages (D) lasting at least 10000 s with a specific input energy of at least 10 W·h / kg. -1 or ultrasonicating the dispersion at a frequency of at least 20 kHz with a specific input energy of at least 1 W·h / kg, and the stationary phase (R) is a step of suspending the dispersion between two successive dispersion phases (D) for at least 1 min, for 10 s. -1 In another embodiment, the method preferably comprises a series of at least 10 dispersion stages (D) and at least 9 alternating stationary stages (R). In another embodiment, the method preferably comprises a series of at least 30 dispersion stages (D) and at least 29 alternating stationary stages (R).

[0044] In some embodiments, one or several devices provide a mechanical processing or ultrasonic treatment step and the dispersion is held for 10 s. -1 A series of at least three (D) stages and at least two stationary stages (R) are alternately carried out by circulating the dispersion between a slowly stirred tank at a shear rate of less than 1000 rpm, where the factor of such dispersion circulation during dispersion production is preferably at least 5. In some process embodiments, the dispersion circulation factor during production can be at least 10. In other embodiments, the dispersion circulation factor during production is preferably at least 30. The preferred number of circulation cycles is defined by the composition of the dispersion, the type of dispersion equipment, and the specific input power at the dispersion stage.

[0045] In some embodiments, the method preferably comprises a specific input energy of at least 10 W·h / kg for at least 10,000 s -1 The ultrasonic processing device is equipped with a rotary pulsating device with a shear rate of 10 s, a frequency of at least 20 kHz and an immersion sonotrode (ultrasonic probe, ultrasonic actuator) with a specific input energy of at least 1 W h / kg, and a residence time of the dispersion in the tank is at least 1 min and the dispersion is heated to 10 s. -1 The method includes circulating the dispersion at a circulation rate of 100 to 10,000 kg / h between a tank that is slowly stirred at a shear rate of less than 10000 s. The residence time refers to the ratio between the tank volume and the circulation rate, i.e., the average residence time of the dispersion in the tank in the approximation of a perfect mixing device. In some embodiments, the shear rate between the rotor and the stator of the rotary pulsator is preferably at least 20,000 s. -1 , most preferably at least 50000s -1 In some embodiments, the specific input energy when the dispersion passes through the rotary pulsator is preferably 30 W·h / kg or less. However, technical results can also be achieved with a specific input energy of 10-30 W·h / kg when the dispersion passes through the rotary pulsator. Also, preferably, the ultrasonic treatment is carried out at a frequency of at least 40 kHz and a specific input energy of more than 2 W·h / kg. However, technical results can also be achieved with a frequency of 20 kHz-40 kHz and a specific input energy of 1-2 W·h / kg, but this requires more cycles.

[0046] In some embodiments, the manufacturing process preferably comprises at least 10,000 s -1 and a specific input energy of at least 10 W·h / kg, and a dispersion mean residence time of at least 1 min and 10 s -1The method includes circulating the dispersion between a tank slowly stirred at a shear rate of less than 70000 s and a tank at a circulation rate of 100 to 10,000 kg / h. The pressure upstream of the homogenizer valve can be more than 30 MPa, for example more than 60 MPa, and is determined by the design of the homogenizer. The nozzle diameter is also determined by the design of the homogenizer, which is outside the scope of the present invention, and can be less than 2 mm, for example 700 μm. In some embodiments, the shear rate between the rotor and stator of the rotary pulsator is preferably less than 70,000 s -1 More than 500,000s, most preferably -1 In some embodiments, the specific input energy at each dispersion stage is preferably greater than 20 W·h / kg, most preferably greater than 30 W·h / kg. However, technical results can also be achieved with a specific input energy at each dispersion stage between 10 and 20 W·h / kg of dispersion, but this would require more cycles.

[0047] In one embodiment, the present invention provides a method for producing a cathode slurry containing a cathode active material, water, a gelling agent, and at least 0.005 wt % of single-walled and / or double-walled carbon nanotubes, the method comprising the steps of (C1) mixing an active lithium-containing component and the dispersion containing water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, wherein the content of single-walled and / or double-walled carbon nanotubes in the dispersion is 0.3-2 wt %, and the weight ratio between the single-walled and / or double-walled carbon nanotubes and the gelling agent in the dispersion is at least 0.05 and not more than 10, and (C2) stirring the resulting mixture to produce a uniform slurry.

[0048] In one embodiment, the present invention provides a cathode slurry containing a cathode active material, water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, the cathode slurry containing at least 0.005% by weight of single-walled and / or double-walled carbon nanotubes and produced by the above-mentioned method.

[0049] In one embodiment, the present invention provides a method for producing an anode slurry containing an anode active material, water, a gelling agent, and at least 0.01 wt % of single-walled and / or double-walled carbon nanotubes, the method comprising the steps of (A1) mixing an active silicon-containing component, and the dispersion containing water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, wherein the content of single-walled and / or double-walled carbon nanotubes in the dispersion is 0.3-2 wt %, and the weight ratio between the single-walled and / or double-walled carbon nanotubes and the gelling agent in the dispersion is at least 0.05 and not more than 10; and (A2) stirring the resulting mixture to produce a uniform slurry.

[0050] In one embodiment, the present invention provides an anode slurry containing a cathode active material, water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, the anode slurry containing at least 0.01% by weight of single-walled and / or double-walled carbon nanotubes and produced by the above method.

[0051] In step (C2) or (A2), the stirring of the mixture obtained in step (C1) or (A1), respectively, to produce a homogeneous suspension can be carried out by any known mixing method with any mixing equipment, such as, but not limited to, a vertical stirrer (also known as a dissolver), a planetary mixer, a rotor-stator type mixer, a twin screw mixer. In some embodiments, the stirring is preferably carried out using a disk dissolver, i.e., a vertical stirrer with a disk impeller, preferably with a toothed disk impeller. In step (C2) or (A2), a planetary mixer is most preferred. It should be noted that the choice of the mixing method for step (C2) or (A2) and the choice of equipment for these steps are outside the scope of the present invention.

[0052] Cathode active material refers to any material that has the following properties (reviewed by MS Whittingham, Lithium Batteries and Cathode Materials, Chem. Rev. 2004, Vol. 104, pp. 4271-4301): (1) the material contains easily reducible / oxidizable ions, e.g., transition metal cations; (2) the material reacts with lithium reversibly without fundamental change in its structure; (3) the material reacts with lithium with a high free energy of reaction (Helmholtz potential); (4) the material interacts with lithium very rapidly. For example, the active material in the cathode slurry is LiTiS 2 , LiVSe 2 , LiCoO 2 , LiNiO 2 , LiFePO 4 (also known as LFP), LiNi x Mn y Co z O 2 (wherein x, y, and z are positive numbers less than 1, and x+y+z=1. This is also called NMC, e.g., LiNi 0.8 Mn 0.1 Co 0.1 O 2 (also called NMC 811), or any other, but not limited to the examples given, or mixtures thereof. The cathode slurry of the present invention comprises LiFePO 4 (also called LFP) is most preferred.

[0053] The anode active material refers to a material that can absorb significant amounts of reduced lithium without fundamentally changing its structure. The anode active material may be a graphite phase, a silicon phase, or silicon oxide (SiO x phase, where x is a positive number less than or equal to 2, or a mixture of silicon and silicon oxide, SiO, in which the total atomic ratio between elemental oxygen and elemental silicon in the anode active material is greater than 0 and less than 1.8. xA combination of phases or other known anode active materials, for example as described in the review by H. Cheng; JG Chapter; Y. Li, G. Gao, Recent progress of advanced anode materials of lithium-ion batteries. Journal of Energy Chemistry, Volume 57, 2021, pp. 451-468, ISSN 2095-4956, doi.org / 10.1016 / j.jechem.2020.08.056.

[0054] The term "electrode slurry," with respect to the provided methods for making the cathode and anode slurries and the provided cathode and anode slurries, shall refer to the cathode slurry or the anode slurry, and "electrode" shall refer to the cathode or the anode, respectively.

[0055] Having both single-walled and / or double-walled carbon nanotubes and a gelling agent in the electrode slurry causes a significant difference in the rheological properties of the slurry from an ideal (Newtonian) fluid in that the flow behavior exponent n of the electrode slurry is small, preferably at least 10 Pa s n The electrode slurry has a flow consistency index K of 0.37 or less, which means that the electrode slurry has a very low viscosity, e.g., a 100 s flow consistency index K typical of the subsequent application of the electrode slurry to a conductive electrode plate. -1 High viscosity, for example 1s -1 and at least 10 Pa·s at a shear rate of less than or equal to 10 Pa·s. This combination of electrode slurry properties is preferred and solves the technical problem of providing high viscosity during storage prior to use (application to the current collector of the electrode), providing high viscosity after application to the current collector without spreading to ensure good quality of the edges of the active material layer of the electrode, and at the same time providing low viscosity of the electrode slurry under defined processing conditions for application to the current collector.

[0056] The electrode slurry may contain another water-soluble organic solvent in addition to water if it is advantageous for processing. The water-soluble organic solvent may include, but is not limited to, N-methyl-2-pyrrolidone, ethylene carbonate, dimethyl sulfoxide, dimethylacetamide, etc. The additional water and / or water-soluble organic solvent may be added in step (C1) or (A1) of mixing the electrode active material with the dispersion containing single-walled and / or double-walled carbon nanotubes and gelling agent, or in an additional mixing step preceding the mixing step (C1) or (A1), or in a separate mixing step after the mixing step (C1) or (A1) and before the step (C2) or (A2).

[0057] To ensure the necessary plasticity and strength of the electrode material after drying, binders can be further added to the electrode slurry. These additives, which are most typically polymeric materials, can be introduced in the form of a solution or suspension, for example an aqueous suspension, a suspension based on N-methyl-2-pyrrolidone or another solvent, the choice of the solvent depending on the characteristics of the process used. These additives can include, for example, suspensions of fluoroplastics, latexes of various rubbers, polyacrylic acid or its salts, for example Na or Li salts. The binder can be added in the step (C1) or (A1) of mixing the electrode active material with the dispersion containing the single-walled and / or double-walled carbon nanotubes and the gelling agent, or in an additional mixing step preceding the mixing step (C1) or (A1), or in a separate mixing step after the mixing step (C1) or (A1) and before the step (C2) or (A2).

[0058] To achieve the technical result, it is important that the dispersion used to prepare the slurry in step (C1) or (A1) contains both a gelling agent and single-walled and / or double-walled carbon nanotubes, i.e. it is not sufficient that the dispersion for preparing the electrode slurry contains single-walled and / or double-walled carbon nanotubes and a gelling agent is added thereto during the preparation of the electrode slurry. In some embodiments, the electrode slurry preferably further contains a gelling agent that is chemically similar to the gelling agent in the dispersion described above, i.e. contains water, a gelling agent and single-walled and / or double-walled carbon nanotubes, and is used to prepare the electrode slurry, or preferably another gelling agent is added to the electrode slurry. In this case, the weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the electrode slurry is smaller than the corresponding ratio in the dispersion used for its preparation. Additional gelling agents, chemically similar to those in the dispersion or different, can be added in step (C1) or (A1) of mixing the electrode active material with the dispersion containing single-walled and / or double-walled carbon nanotubes, or can be added in an additional mixing step preceding mixing step (C1) or (A1), or can be added in a separate mixing step after mixing step (C1) or (A1) and before step (C2) or (A2).

[0059] To summarise the above three paragraphs, the method of producing an electrode slurry may comprise one or several additional steps of mixing with water and / or a water-soluble organic solvent and / or one or several binders and / or conductive additives prior to step (C2) or (A2). In some embodiments, a solvent and / or one or several binders and / or conductive additives are also added to the mixture, preferably in the mixing step (C1) or (A1).

[0060] It should be noted that the substance that acts as a gelling agent to change the rheological properties of the electrode slurry as described above can also function as a binder; for example, a Li salt of polyacrylic acid is both a gelling agent that has a synergistic effect on the rheological properties of slurries containing single-walled and / or double-walled carbon nanotubes, and a binder that improves the strength properties of the electrode slurry.

[0061] The preferred weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the electrode slurry is at least 0.005 and not more than 10. In some embodiments, the weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the electrode slurry is preferably at least 0.01 and not more than 5. The most preferred weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the electrode slurry is at least 0.03 and not more than 3. However, synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the electrode slurry in the range of 0.005-0.03. Synergistic effects leading to technical results can also be achieved with a weight ratio of single-walled and / or double-walled carbon nanotubes to gelling agent in the electrode slurry in the range of 3-10.

[0062] In some embodiments, the electrode slurry preferably further contains at least 0.1 wt. % of conductive additives other than single-walled and / or double-walled carbon nanotubes, such as, but not limited to, graphite, carbon black, acetylene black, carbon fibers of various morphologies, thicknesses and lengths, or metal particles, for example, such additives can ensure another benefit of reducing the internal resistance of the electrode.

[0063] The electrode slurry may contain metal particles from Groups 8 to 11 of the Periodic Table of Elements that are impurities in the single-walled and / or double-walled carbon nanotubes resulting from the carbon nanotube manufacturing process. These conductive additives, including metal particles, do not prevent the achievement of the technical result. However, it should be noted that metal particles are undesirable in most embodiments, and the content of metal impurities from Groups 8 to 11 of the Periodic Table of Elements in the electrode slurry is preferably less than 1% by weight of the single-walled and double-walled carbon nanotubes. In some embodiments, the content of metal impurities from Groups 8 to 11 of the Periodic Table of Elements in the electrode slurry is preferably less than 0.1% by weight of the single-walled and double-walled carbon nanotubes.

[0064] In one embodiment, the present invention provides a method for producing a lithium-ion battery cathode, characterized in that the method includes a series of steps for producing the cathode slurry: (C1) mixing the active lithium-containing cathode components and the dispersion containing water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, where the content of single-walled and / or double-walled carbon nanotubes in the dispersion is 0.3-2 wt %, and the weight ratio between the single-walled and / or double-walled carbon nanotubes to the gelling agent in the dispersion is at least 0.05 and not more than 10, (C2) stirring the resulting mixture to produce a uniform slurry, and (C3) applying the resulting slurry to a current collector, (C4) drying the applied slurry until a cathode is formed, and (C5) compressing the cathode to a required density. The method of making the cathode can include an additional step of introducing a binder and / or additional solvent and / or gelling agent chemically similar to those in the dispersion or different, which can be added in the step of mixing (C1) the active lithium-containing cathode material with the dispersion containing single-walled and / or double-walled carbon nanotubes and a gelling agent, or can be added in a separate mixing step preceding mixing step (C1), or can be added in a separate mixing step after mixing step (C1) and before step (C2).

[0065] In one embodiment, the present invention provides a method for producing a lithium-ion battery anode, the method comprising a series of steps for producing the anode slurry: (A1) mixing the active anode components and the dispersion containing water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, the content of single-walled and / or double-walled carbon nanotubes in the dispersion being 0.3-2 wt %, and the weight ratio between the single-walled and / or double-walled carbon nanotubes to the gelling agent in the dispersion being at least 0.05 and not more than 10, (A2) stirring the resulting mixture to produce a uniform slurry, and (A3) applying the resulting slurry to a current collector, (A4) drying the applied slurry until the anode is formed, and (A5) compressing the anode to a required density. The method of making an anode can include an additional step of introducing a binder and / or additional solvent and / or gelling agent chemically similar to those in the dispersion or different, which can be added in the step of mixing (A1) the anode active material with the dispersion containing single-walled and / or double-walled carbon nanotubes and gelling agent, or can be added in a separate mixing step preceding mixing step (A1), or can be added in a separate mixing step after mixing step (A1) and before step (A2).

[0066] In one embodiment, the present invention provides a lithium-ion battery cathode produced by a process comprising a series of steps for producing the cathode slurry: (C1) mixing the dispersion containing an active lithium-containing component and water, a gelling agent, and single-walled or double-walled carbon nanotubes, wherein the content of single-walled and / or double-walled carbon nanotubes in the dispersion is 0.3-2 wt %, and the weight ratio between the single-walled and / or double-walled carbon nanotubes to the gelling agent is at least 0.05 and not more than 10, (C2) stirring the resulting mixture to produce a uniform slurry, and (C3) applying the resulting slurry to a current collector, (C4) drying the applied slurry until a cathode is formed, and (C5) compressing the cathode to a required density.

[0067] By having both gelling agent and single-walled and / or double-walled carbon nanotubes in the cathode slurry, the viscosity as a function of shear rate is affected, ensuring both stability and moderate viscosity of the cathode slurry under the application conditions to the current collector, and the lithium ion battery having the cathode of the present invention exhibits very stable operation in successive charge-discharge cycles. For example, the battery capacity after 400 charge-discharge cycles at a current of 1C can be more than 80%, in some embodiments more than 90%, and in some embodiments more than 95% of the initial battery capacity. The achievable battery stability depends on the active material in the battery cathode and the battery anode.

[0068] In one embodiment, the present invention provides a lithium-ion battery anode, characterized in that it is produced by a method including a series of steps for producing the anode slurry, including: (A1) mixing the dispersion containing the active anode components and water, a gelling agent, and single-walled and / or double-walled carbon nanotubes, wherein the content of single-walled and / or double-walled carbon nanotubes in the dispersion is 0.3-2 wt %, and the weight ratio between the single-walled and / or double-walled carbon nanotubes to the gelling agent is at least 0.05 and not more than 10, (A2) stirring the resulting mixture to produce a uniform slurry, and (A3) applying the resulting slurry to a current collector, (A4) drying the applied slurry until an anode is formed, and (A5) compressing the anode to a required density.

[0069] By having both gelling agent and single-walled and / or double-walled carbon nanotubes in the anode slurry, which affects the viscosity as a function of shear rate and ensures both a stable and moderate viscosity of the anode slurry under the application conditions to the current collector, lithium ion batteries with the anode of the present invention exhibit very stable operation in successive charge-discharge cycles. For example, the battery capacity after 400 charge-discharge cycles at a rate of 1C can be more than 80%, in some embodiments more than 90%, and in some embodiments more than 95% of the initial battery capacity. The achievable battery stability depends on the active material in the battery anode and the battery cathode.

[0070] The present invention is illustrated by the accompanying figures and examples, which are provided for illustrative purposes only and are not intended to limit the possible embodiments of the present invention. For convenience, basic information regarding the examples is also summarized in Tables 1 and 2, which provide information on the composition and properties of the dispersions and electrode slurries.

[0071] Additional features and advantages of the invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by the practice of the invention. The advantages of the invention will be realized and attained by the structure particularly pointed out in the written description and claims hereof, as well as the appended drawings.

[0072] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory and are intended to provide further explanation of the invention as claimed. Brief Description of the Accompanying Drawings

[0073] The accompanying drawings, which are included to provide a further understanding of the invention, and which are incorporated in and constitute a part of this specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention. [Brief description of the drawings]

[0074] [Figure 1]1 shows transmission electron micrographs of Tuball™ single-walled carbon nanotubes in dispersions of Examples 1, 5, and 7, and Comparative Example 8. [Diagram 2] The dynamic viscosity (Pa·s) of the dispersions of Example 1 (circles), Example 2 (squares), and Comparative Example 8 (dark triangles) is shown as a function of shear rate (s-1). [Diagram 3] FIG. 1 shows the dynamic viscosity (Pa s) as a function of shear rate (s-1) for the cathode slurries of Example 1 (circles) and Comparative Example 8 (dark squares), and the anode slurries of Example 1 (diamonds) and Comparative Example 8 (dark triangles). [Figure 4] Photographs of cathode slurry layers applied to current collectors in Example 1 (left) and Comparative Example 8 (right) are shown. [Diagram 5] 1 shows the capacity relative to the initial capacity as a function of the number of charge / discharge cycles (charge rate 1C, discharge rate 1C) of a lithium ion battery having the cathode and anode of Example 1. [Figure 6] 1 shows the capacity relative to the initial capacity as a function of the number of charge / discharge cycles (charge rate 1C, discharge rate 1C) of a lithium ion battery having the cathode and anode of Example 2. [Figure 7] 1 shows the capacity relative to the initial capacity as a function of the number of charge / discharge cycles (charge rate 1C, discharge rate 1C) of a lithium ion battery having the cathode and anode of Example 3. [Figure 8] 1 shows a transmission electron microscope photograph of single-walled and double-walled carbon nanotubes of the dispersion of Example 4. [Figure 9] 1 shows the capacity relative to the initial capacity as a function of the number of charge / discharge cycles (charge rate 1C, discharge rate 1C) of a lithium ion battery having the cathode and anode of Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0075] Reference will now be made in detail to the preferred embodiments of the invention, examples of which are illustrated in the accompanying drawings.

[0076] Example 1 Dispersion preparation and description. The dispersion contains 0.6 wt% Na-carboxymethylcellulose as a gelling agent and 0.4 wt% single-walled carbon nanotubes and their aggregates in water. The single-walled carbon nanotubes used to prepare the dispersion are Tuball™ SWCNTs. The diameter of the SWCNTs ranges from 1.2 to 2.1 nm, with an average diameter of 1.54 nm (the diameter was determined by TEM of the dried suspension, and is represented by the absorption band S in the optical absorption spectrum of the suspension). 1-1 Raman spectroscopy at 532 nm revealed a peak at 1580 cm typical of single-walled carbon nanotubes. -1 Strong G lines at around 1330 cm and other allotropic forms of carbon and defects in single-walled carbon nanotubes. -1 The G / D line intensity ratio is 80. The specific surface area determined from the nitrogen adsorption isotherm is 1220 m 2 / g. For a transmission electron micrograph of the SWCNTs used, see FIG. 1. The SWCNTs for producing the dispersion were further modified with chlorine by the method described in the present invention [RU2717516C2; MCD TECH, March 23, 2020; IPC: C01B32 / 174, B82B3 / 00, B82B1 / 00]. Energy dispersive spectroscopy shows that the chlorine content in the tubular SWCNTs is 0.25 wt.%. %. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) shows that the SWCNTs contain 0.46 wt.% iron (group 8 metal) impurity. The weight ratio of single-walled carbon nanotubes to gelling agent in the slurry is 0.667.

[0077] Dispersions were prepared by mixing the required proportions of water, carboxymethylcellulose Na salt and SWCNTs and dispersing 10 times in a NETZSCH Omega 500 high-pressure homogenizer through a nozzle with a diameter of 700 μm at a pressure of 65 MPa and a dispersion transfer rate of 300 kg / h. The shear rate in the nozzle was approximately 6·10 5 s -1The power consumption was 8 kW, and the specific input energy in stage (D) was about 27 W·h / kg. Between each of the two dispersion stages, the dispersion was placed in a 50 L tank and stirred for about 1 s by a gate agitator. -1 The mixture was stirred slowly for 10 minutes at a shear rate of 0.05.

[0078] The rheological properties of the dispersions were measured with a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 912 Pa and the loss modulus G'' = 190 Pa, meaning that the dispersion is a highly viscous gel.

[0079] The dispersion is subjected to shear rate (s -1 The viscosity is characterized by the viscosity (Pa·s) as a function of shear rate. The viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity as a function of shear rate was 0.093 s -1 ~93s -1 The flow behavior index n is 0.13 and the flow consistency index is 9.0 Pa s 0.13 1 / 6.3s -1 The dispersion viscosity at low shear rates below 43 Pa s is greater than 18.6 s. -1 In the region of shear rates above 0.72 Pa s, the shear rate is less than 0.72 Pa s.

[0080] The dispersion is used to prepare a cathode slurry and a cathode.

[0081] Using the dispersion, 58.65 wt% of the active material LiFePO4 A cathode slurry was prepared containing 40 wt.% water as a solvent, 0.72 wt.% styrene butadiene rubber binder, 0.6 wt.% Na-carboxymethyl cellulose gelling agent, and 0.03 wt.% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - 54 g of a solution containing 0.925 g of Na-carboxymethylcellulose and 53.075 g of water are added to 12.5 g of this dispersion and mixed for 30 minutes on an overhead stirrer (additional steps of adding binder and solvent carried out before step (C1) and before step (C2)); - The resulting mixture was mixed with 97.75 g of the active ingredient LiFePO 4 and mixing (step C1); - adding 2.4 g of an aqueous styrene-butadiene rubber latex with a dry matter content of 50% (additional binder addition step carried out before step (C2)); - Stir for 16 hours to produce a homogenous slurry (Step C2).

[0082] Due to both the single-walled carbon nanotubes and the gelling agent in the dispersion used to prepare the slurry, the resulting cathode slurry has a sharp and pronounced dependence of viscosity on shear rate represented by the circle (curve 1C) in FIG. 3. The flow behavior index is 0.26. -1 The viscosity measured at a shear rate of 100 s was 0.76 Pa s. -1 Extrapolation of the shear rate dependence of gives a viscosity estimate of about 0.70 Pa s, which provides a process capacity for application to the current collector plate. -1 At shear rates below 100 nm, the viscosity exceeds 21 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0083] The storage stability of the slurries was determined by varying the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids and kept under standard conditions (atmospheric pressure, 25 ° C) for 7 days. The upper third, middle third and lower third of the test tube were then sampled with a pipette and the weight fraction of water and solid non-volatile components in the samples was determined by drying. For the cathode slurry of this example, the water content in the initial slurry was 40.0 wt.%, and after one week of storage, the solvent content was 41.0 wt.% in the upper third, 39.8 wt.% in the middle and 39.2 wt.% in the lower third. The relative difference with the initial solvent content did not exceed 2.5%, which is significantly smaller than the slurry described in Comparative Example 8 below, indicating the high stability of the resulting slurry. The slurry can be used to manufacture cathodes after 7 days of storage.

[0084] The lithium-ion battery cathode was prepared by applying the obtained slurry to an aluminum foil current collector, drying the applied slurry until a cathode was formed, and calendering the cathode with a force of 5 tons to obtain a thickness of 2.5 mg / cm. 2 The cathode slurry was fabricated by compressing it to the required density of 10 ... 6 The initial specific capacity of the cathode at a discharge current of 0.015 A / g of the cathode material is 158 mA·h / g of the cathode material. The dispersion is used to prepare an anode slurry and an anode.

[0085] The dispersion was used to prepare an anode slurry containing 31.3 wt.% graphite active material, 14.2 wt.% silicon active material, 53.6 wt.% water solvent, 0.35 wt.% Na-carboxymethylcellulose gelling agent, 0.84 wt.% styrene butadiene latex binder, and 0.23 wt.% single-walled carbon nanotubes. The anode slurry was prepared by the following sequence of steps: - 187.5 g of dispersion, 1500 g of water, 1000 g of graphite powder and 454.2 g of silicon powder are mixed and stirred for 10 hours (stage A1 in which additional water is introduced); - 54 g of a 50% by weight aqueous styrene butadiene latex suspension (an additional binder addition step carried out before step (A2)); - Stir for 4 hours to produce a homogenous slurry (Step A2).

[0086] Due to the presence of both the single-walled carbon nanotubes and the gelling agent, the resulting anode slurry also has a sharply pronounced dependence of viscosity on shear rate represented by the diamond (curve 1A) in Figure 3. The dependence follows an Ostwald-de Waele power law with a flow behavior index of 0.17 and a flow consistency index of 11.5 Pa s 0.17 100s -1 At a shear rate of 1s, the slurry viscosity is less than 0.26 Pa·s, which provides process capacity for application to the current collector plate. -1 At shear rates below 100° C., the viscosity exceeds 11.6 Pa·s, which ensures the stability of the slurry during storage before use and the stability of the slurry layer on the current collector before drying.

[0087] The storage stability of the anode slurry was tested by the method described above for the cathode slurry. Within one week, the water content of the top third of the slurry increased from 53.6% to 54.2% by weight (i.e., less than 2% relative to the initial value), indicating high slurry stability.

[0088] For the manufacture of the anode, the resulting anode slurry was applied to a copper foil using a doctor blade, dried for 1 hour at a temperature of 40°C and calendered at a force of 5 tons at 1.4 g / cm 3 The anode material density was 8.5 mg / cm. 2 The anode characteristics were measured using a cell with a Li cathode and a Li reference electrode, and LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 The initial specific capacity of the anode at a charging current of 0.03 A / g of the anode material is 342 mA·h / g of the anode material.

[0089] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 0.8M solution of 1% v / v vinyl carbonate was added to the electrolyte. The initial battery capacity at a discharge rate of 0.1C was 324mA. . The capacity (referred to as the initial capacity) as a function of the number of charge-discharge cycles (charge current 324 mA, discharge current 324 mA) is shown in Figure 5. The battery capacity exceeds 90% of the initial capacity after 3000 cycles.

[0090] Example 2 The dispersion contains 0.6 wt.% polyvinylpyrrolidone (PVP) gelling agent, 0.3 wt.% single-walled carbon nanotubes and their aggregates, and the remainder is water. The dispersion was prepared using Tuball™ SWCNTs that were subjected to multi-stage chemical purification and boiled in nitric acid for 4 hours. Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) indicates that the Fe content in the SWCNTs is 60 ppm or 0.06 wt.%. Potentiometric titration indicates that the SWCNT surface after such treatment contains about 0.62 wt.% carboxyl groups. The diameters of the SWCNTs are distributed in the range of 1.2-2.1 nm, with an average diameter of 1.60 nm, a G / D line intensity ratio of 24, and a specific surface area determined from a nitrogen adsorption isotherm of 1280 m 2 The weight ratio of single-walled carbon nanotubes to gelling agent in the slurry is 0.667.

[0091] Mix the required proportions of water, polyvinylpyrrolidone and SWCNTs and disperse them in a Chaoli GJB500 high-pressure homogenizer and a gate agitator for about 1 s. -1 The dispersion was prepared by repeating eight alternating steps of standing in a 65 liter tank with slow stirring for 12 min at a shear rate of 0.05 to 0.05 mm. The dispersion was carried out at a pressure of 60 MPa, a dispersion transfer flow rate of 300 l / h, and a pH of approximately 6·10. 5 s -1 The measured power consumption was 16 kW and the specific input energy in stage (D) was about 53 W h / kg.

[0092] The rheological properties of the dispersions were measured with a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 2460 Pa and the loss modulus G'' = 390 Pa, meaning that the dispersion is a highly viscous gel.

[0093] The dispersions were subjected to shear rate (s -1 It is characterized by its viscosity (Pa s) as a function of temperature. The flow behavior index n is 0.156 and the flow consistency index is 21.6 Pa s 0.156 1 / 6.3s -1 The dispersion viscosity in the low shear rate region is greater than 100 Pa s and is 18.6 s -1 In the region of shear rates above 1.9 Pa s, the shear strength is less than 1.9 Pa s.

[0094] Using the dispersion, 61 wt. % of the active material LiNi 0.33 Co 0.33 Mn 0.33 O 2 A cathode slurry was prepared containing (NCM111), 37.7 wt% water solvent, 0.62 wt% styrene butadiene rubber binder, 0.62 wt% Na-carboxymethyl cellulose binder, 0.047 wt% PVP gelling agent, and 0.023 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - 240 g of a solution containing 5 g of Na-carboxymethylcellulose and 235 g of water is added to 62.5 g of this dispersion and mixed for 30 minutes on an overhead stirrer (step of adding additional binder and solvent carried out before step (C1) and before step (C2)). - The mixture obtained is mixed with 488 g of active ingredient NCM111 (step C1); - adding 10 g of an aqueous styrene-butadiene rubber latex with a dry matter content of 50% (additional binder addition step carried out before step (C2)); - Stir for 16 hours to produce a homogenous slurry (Step C2).

[0095] Due to both the single-walled carbon nanotubes and the gelling agent in the dispersion used to prepare the slurry, the resulting cathode slurry has a sharply significant dependence of viscosity on shear rate, which is well described by a power law with a flow behavior index of 0.24 and a flow consistency index of 18.8 Pa s. -1 At a shear rate of 1s, the dynamic viscosity is about 0.55 Pa s, which provides process capacity for application to the current collector plate. -1 At the following shear rates, the viscosity is at least 18.8 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0096] The storage stability of the slurry was determined by the method described in Example 1. For the cathode slurry of this example, the water content in the initial slurry was 37.7 wt%, and after one week of storage, the water content was 38.2 wt% in the upper third, 37.9 wt% in the middle, and 37.0 wt% in the lower third. The relative difference with the initial solvent content did not exceed 2%, within the measurement error. The slurry can be used to fabricate a cathode after 7 days of storage.

[0097] The lithium-ion battery cathode was prepared by applying the resulting slurry to an aluminum foil current collector, drying the applied slurry until a cathode was formed, and calendering the cathode at a force of 5 tons to a density of 3.6 mg / cm. 2 The cathode properties were evaluated by compressing the Li cathode and Li reference electrode in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6The initial specific capacity of the cathode material was determined by assembling an electrolyte containing a 1M solution of 0.015 A / g of vinyl carbonate and an additional 1% v / v of vinyl carbonate. . h / g.

[0098] The dispersion was used to prepare an anode slurry containing 26.6 wt.% graphite active material, 16.2 wt.% silicon active material, 55.5 wt.% water solvent, 0.33 wt.% polyvinylpyrrolidone gelling agent, 0.49 wt.% Na-carboxymethylcellulose binder, 0.66 wt.% styrene butadiene latex binder, and 0.17 wt.% single-walled carbon nanotubes. The anode slurry was prepared by the following sequence of steps: - 367 g of silicon powder and 600 g of graphite powder are added to 1250 g of the dispersion and stirred for 1 hour (step (A1)); - adding 11 g of Na-carboxymethylcellulose powder and stirring for 1 hour; (step of adding additional binder carried out before step (A2)); - 30 g of a 50% by weight aqueous butadiene styrene latex suspension (an additional binder addition step carried out before step (A2)); - Stir for 16 hours to produce a homogenous slurry (Step A2).

[0099] For the manufacture of the anode, the resulting anode slurry was applied to a copper foil using a doctor blade, dried at a temperature of 80°C for 15 minutes, and calendered at a force of 5 tons at 1.0 g / cm. 3 The anode properties were evaluated by measuring the density of the anode material in a cell with a Li cathode and Li reference electrode and LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 The initial specific capacity of the anode at a charging current of 0.3 A / g of the anode material is 1360 mA·h / g of the anode material.

[0100] When both single-walled carbon nanotubes and gelling agent were present, the resulting anode slurry had a sharp and significant dependence of viscosity on shear rate, which was shown to have a flow behavior index of 0.19 and a flow consistency index of 12.3 Pa s 0.19 It follows the Ostwald-de Waele power law with 100s -1 At a shear rate of 1s, the slurry viscosity is less than 0.30 Pa·s, which provides process capacity for application to the current collector plate. -1 At shear rates below 100°C, the viscosity exceeds 12.3 Pa·s, which ensures the stability of the slurry during storage before use and the stability of the slurry layer on the current collector before drying.

[0101] The storage stability of the anode slurry was tested by the method described above for the cathode slurry. Within one week, the water content of the top third of the slurry increased from 55.6 wt.% to 57.0 wt.% (i.e., 3 rel.% less than the initial value), indicating high slurry stability.

[0102] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 1.5 M solution of 1.0% EDTA with 20% v / v vinyl carbonate was used as the electrolyte. The initial battery capacity was 525 mA·h at a discharge rate of 0.1 C. The capacity as a function of the number of charge-discharge cycles (charge current 525 mA, discharge current 525 mA), referred to as the initial capacity, is shown in Figure 6. The battery capacity exceeds 96% of the initial capacity after 1000 cycles. Example 3

[0103] The dispersion contains 2 wt. % polyacrylic acid Na salt gelling agent, 0.3 wt. % single-walled carbon nanotubes and their aggregates, and the remainder is water. The single-walled carbon nanotubes used to prepare the dispersion are Tuball™ SWCNTs. The SWCNTs have a diameter distribution in the range of 1.2-2.1 nm, an average diameter of 1.62 nm, a G / D line intensity ratio of 46, and a specific surface area determined from a nitrogen adsorption isotherm of 580 m. 2 Thermogravimetric data in 5% oxygen flow in Ar indicates that the ash content is about 20 wt% after oxidation of the material at 950 °C. X-ray diffraction shows that the ash is mainly iron oxide, Fe 2 O 3 %, indicating that the SWCNTs contain nano-dispersed metallic iron phases. Energy dispersive X-ray spectroscopy indicates that the Fe content in the SWCNTs is 14.2 wt%, which is consistent with the ash weight data.

[0104] The dispersion was prepared by mixing the required proportions of water, Na-salt of polyacrylic acid, and SWCNTs, dispersing in a rotary pulsating apparatus (RPA) with a power consumption of 32 kW, a rotor diameter of 190 mm, a gap between the rotor and stator of 700 μm, and a rotor speed of 2940 rpm, sonicating in a 100 L tank at a frequency of 40 kHz and an acoustic input power of 1800 W sonotrode, and stirring in a 220 L tank at 30 rpm and approximately 2 s by an anchor agitator. -1 The dispersion was prepared by repeating 15 alternating stages of slow stirring and settling at a shear rate of 1000 kg / h; the rate of dispersion circulation between the RPA, the probe sonicator, and the tank was 1000 kg / h; about 32 W·h / kg of energy was applied to the dispersion in the RPA in the dispersion stage (D); about 1.8 W·h / kg was applied to the dispersion in the ultrasonic treatment stage (D); about 2 s -1 The average tank residence time of the dispersion at a shear rate of about 13 minutes in stage (R).

[0105] The rheological properties of the dispersions were measured with a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 1150 Pa and the loss modulus G'' = 410 Pa, meaning that the dispersion is a highly viscous gel.

[0106] The dispersion is characterized by a rapid decrease in viscosity at higher shear rates, which is well described by a power law. The flow behavior index n is 0.23 and the flow consistency index is 19.0 Pa s 0.23 The dispersion viscosity is 1 / 6.3s. -1 In the low shear rate region below 78 Pa s, the shear rate exceeds 18.6 s -1 and the shear rate range above 0.53 Pa s, which provides, on the one hand, high dispersion storage stability and, on the other hand, its processability in various embodiments, including the preparation of electrode slurries for producing lithium-ion battery electrodes.

[0107] The dispersion was used to prepare a 29.9 wt. % active material LiCo 2 O 4 A cathode slurry was prepared containing (LCO), 68.6 wt. % water solvent, 1.25 wt. % Na-PAA gelling agent, and 0.19 wt. % single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - 235 g of water is added to 2000 g of the dispersion and mixed for 30 minutes on an overhead stirrer (step of adding additional solvent carried out before step (C1) and before step (C2)). - Mix the mixture obtained with 954 g of active ingredient LCO (step C1); - Stir for 16 hours to produce a homogenous slurry (Step C2).

[0108] Due to both the single-walled carbon nanotubes and the gelling agent in the dispersion used to prepare the slurry, the resulting cathode slurry has a sharp and significant dependence of viscosity on shear rate, which is represented by a flow behavior index of 0.20 and a flow consistency index of 12.1 Pa s 0.2 This is well described by a power law with -1 At a shear rate of 1s, the dynamic viscosity is about 0.30 Pa s, which provides process capacity for application to the current collector plate. -1 At the following shear rates, the viscosity is at least 12.1 Pa·s, which ensures slurry stability during storage before use and stability of the slurry layer on the current collector before drying.

[0109] The storage stability of the slurry was determined by the method described in Example 1. For the cathode slurry of this example, the water content in the initial slurry was 68.6 wt.%, and after one week of storage, the water content was 70.2 wt.% in the upper third, 69.0 wt.% in the middle, and 66.4 wt.% in the lower third. The difference from the initial content of the solvent did not exceed 3.5 rel.%. The slurry can be used to fabricate cathodes after seven days of storage.

[0110] The lithium-ion battery cathode was prepared by applying the obtained slurry to an aluminum foil current collector, drying the applied slurry until a cathode was formed, and calendering the cathode with a force of 10 tons to obtain a thickness of 4.2 mg / cm. 2 The cathode properties were evaluated by compressing the Li cathode and Li reference electrode in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 The initial specific capacity of the cathode at a discharge current of 0.0125 A / g of the cathode material is 123 mA·h / g of the cathode material.

[0111] The dispersion was used to prepare a 18.5 wt. % silicon oxide (SiO x An anode slurry was prepared containing the 0.1 wt. % active material, 79.7 wt. % water solvent, 1.63 wt. % PAA gelling agent, and 0.24 wt. % single-walled carbon nanotubes. The anode slurry was prepared by the following sequence of steps: - 800 g of this dispersion was mixed with SiO x Add 181 g of powder (Step A1); - Stir for 16 hours to produce a homogenous slurry (Step A2).

[0112] When both single-walled carbon nanotubes and gelling agent were present, the resulting anode slurry had a sharp and significant dependence of viscosity on shear rate, which was shown to have a flow behavior index of 0.17 and a flow consistency index of 10.5 Pa s 0.17 It follows the Ostwald-de Waele power law with 100s -1 At a shear rate of 1s, the slurry viscosity is less than 0.23 Pa·s, which provides process capacity for application to the current collector plate. -1 At shear rates below 10.5 Pa·s, the viscosity exceeds 10.5 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0113] The storage stability of the anode slurry was tested by the method described above for the cathode slurry. Within one week, the water content of the top third of the slurry increased from 80% to 81% by weight (i.e., less than 2 rel.% of the initial value), indicating high slurry stability.

[0114] For the manufacture of the anode, the resulting anode slurry was applied to a copper foil using a doctor blade, dried for 15 minutes at a temperature of 70°C, and calendered at a force of 5 tons at 1.3 g / cm 3 The anode properties were evaluated by measuring the density of the anode material in a cell with a Li cathode and Li reference electrode and LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6The initial specific capacity of the anode material at a charging current of 0.1 A / g was determined by assembling an electrolyte containing a 1 M solution of 10% v / v fluoroethylene carbonate. . h / g.

[0115] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 1.5M solution of 20% v / v fluoroethylene carbonate was added and used as the electrolyte. The initial battery capacity at a discharge rate of 0.1C was 1200mA. . The capacity (referred to as the initial capacity) as a function of the number of charge-discharge cycles (charge current 1200 mA, discharge current 1200 mA) is shown in Figure 7. The battery capacity exceeds 85% of the initial capacity after 215 cycles. Example 4

[0116] The dispersion is similar to that described in Example 1, but contains a mixture of single-walled and double-walled carbon nanotubes with diameters between 1.2 and 2.8 nm and an average diameter of 1.8 nm (diameters were determined by TEM of the dried suspension and from the position of the radial breathing mode (RBM) lines in the Raman spectrum). The intensity ratio of the G / D lines in the Raman spectrum of light with a wavelength of 532 nm is 34. The availability of double-walled carbon nanotubes bundled together with single-walled carbon nanotubes is confirmed by the electron micrograph provided in FIG. 8. The concentration of carbon nanotubes in the dispersion is 0.4% by weight. The dispersion also contains 0.6% by weight of carboxymethylcellulose Na salt gelling agent. The weight ratio of single-walled carbon nanotubes to gelling agent in the slurry is 0.667.

[0117] Dispersions were prepared by mixing the required proportions of water, Na-carboxymethylcellulose, and SWCNT and DWCNT, and dispersing 32 times in a NETZSCH Omega 500 high-pressure homogenizer through a nozzle with a diameter of 700 μm at a pressure of 65 MPa and a dispersion transfer rate of 300 kg / h. The shear rate in the nozzle was approximately 6·10 5 s -1 The power consumption was 8 kW, and the specific input energy in stage (D) was about 27 W·h / kg. Between each of the two dispersion stages, the dispersion was placed in a 50 L tank and stirred for about 1 s by a gate agitator. -1 The mixture was stirred slowly for 10 minutes at a shear rate of 0.05.

[0118] The dispersion is characterized by a decrease in viscosity as the shear rate increases. Viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity as a function of shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.19 and the flow consistency index is 4.9 Pa s 0.19 1 / 6.3s -1 The dispersion viscosity at low shear rates below 18.6 s exceeds 22 Pa s. -1 In the region of shear rate above 0.46 Pa s, the shear rate is less than 0.46 Pa s.

[0119] The rheological properties of the dispersions were measured using a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 176 Pa and the loss modulus G'' = 28 Pa, meaning that the dispersion is a highly viscous gel.

[0120] Using the dispersion, 58.65 wt% of the active material LiFePO 4 A cathode slurry containing 40 wt% water solvent, 0.72 wt% styrene butadiene rubber binder, 0.6 wt% Na-carboxymethylcellulose gelling agent, and 0.03 wt% single-walled and double-walled carbon nanotubes was prepared. The preparation procedure was the same as in Example 1.

[0121] Due to both the single-walled and double-walled carbon nanotubes in the dispersion and the gelling agent used to prepare the slurry, the resulting cathode slurry has a sharply significant dependence of viscosity on shear rate, which is well described by a power law. The flow behavior index is 0.29 and the flow consistency index is 18 Pa s. 0.29 93s -1 The viscosity measured at a shear rate of 100 s was 0.72 Pa s. -1 Extrapolation of the shear rate dependence of gives a viscosity estimate of about 0.68 Pa s, which provides a process capacity for application to the current collector plate. -1 At the following shear rates, the viscosity is at least 18 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0122] The storage stability of the slurry was determined as in Example 1. The water content in the initial slurry was 40.0 wt.%, and after one week of storage, the solvent content was 41.4 wt.% in the top third, 39.7 wt.% in the middle, and 38.8 wt.% in the bottom. The difference from the initial solvent content did not exceed 3 rel.%, which is significantly smaller than the slurry described in Comparative Example 8 below, indicating the high stability of the resulting slurry. The slurry can be used to manufacture cathodes after seven days of storage.

[0123] A lithium-ion battery cathode was prepared in the same manner as in Example 1. The initial specific capacity of the cathode material at a discharge current of 0.015 A / g is 152 mA·h / g of the cathode material.

[0124] The dispersion was used to prepare an anode slurry containing 31.3 wt% graphite active material, 14.2 wt% silicon active material, 53.6 wt% water solvent, 0.35 wt% Na-carboxymethylcellulose gelling agent, 0.84 wt% styrene butadiene latex binder, and 0.23 wt% single-walled and double-walled carbon nanotubes. The preparation procedure of the anode slurry was the same as that of Example 1.

[0125] With both the SWNTs and the gelling agent in the dispersion, the resulting anode slurry has a sharply significant dependence of viscosity on shear rate, which can be described by a power law. The flow behavior index is 0.2 and the flow consistency index is 11.0 Pa s 0.2 It is. -1 At a shear rate of 1s, the slurry viscosity is less than 0.28 Pa·s, which provides process capacity for application to the current collector plate. -1 At shear rates below 10.0 Pa·s, the viscosity exceeds 11.0 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0126] The storage stability of the anode slurry was tested by the method described above in Example 1. Within one week, the water content of the top third of the slurry increased from 53.6 wt.% to 54.7 wt.% (i.e., 2 rel.% less than the initial value), indicating high slurry stability.

[0127] An anode was produced in the same manner as in Example 1. The initial specific capacity of the anode at a charging current of 0.03 A / g of the anode material was 334 mA·h / g of the anode material.

[0128] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 0.8 M solution of 1% v / v vinyl carbonate was added and used as the electrolyte. The initial battery capacity was 314 mA·h at a discharge rate of 0.03 C. The battery capacity after 400 charge-discharge cycles was more than 92% of the initial capacity (charge current 314 mA, discharge current 314 mA). Example 5

[0129] The dispersion contains 0.2 wt% carboxymethylcellulose Li salt gelling agent and 2 wt% single-walled carbon nanotubes and their aggregates in water. The dispersion was made using chlorine-modified Tuball™ SWCNTs as described in Example 1. The weight ratio of single-walled carbon nanotubes to gelling agent in the slurry is 10.

[0130] The required proportions of water, polyvinylpyrrolidone and SWCNTs were mixed and the dispersion was mixed for approximately 2 s between a Chaoli GJB500 high pressure disperser (stage (D)) and a 50 liter tank (stage (R)) where the dispersion was stationary. -1 The dispersion was prepared by circulating the mixture 32 times at a dispersion transfer rate of 300 kg / h while slowly stirring with a gate agitator at a shear rate of 100000 s. The estimated shear rate in the disperser was 600000 s. -1The measured power consumption was 19 kW. The specific input energy in the dispersion cycle was about 63 W·h / kg. The average residence time in the tank in stage (R) was about 10 min.

[0131] The viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity as a function of shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.33 and the flow consistency index is 13.5 Pa s 0.33 1 / 6.3s -1 The dispersion viscosity at low shear rates is greater than 45 Pa s and is less than 18.6 s. -1 In the region of shear rates above 1.9 Pa s, the shear strength is less than 1.9 Pa s.

[0132] The rheological properties of the dispersions were measured with a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 980 Pa and the loss modulus G'' = 460 Pa, meaning that the dispersion is a highly viscous gel.

[0133] Using the dispersion, 55.1 wt% of the active material LiFePO 4 A cathode slurry was prepared containing 42.3 wt% water solvent, 0.57 wt% styrene butadiene rubber binder, 1.22 wt% carboxymethyl cellulose Li salt gelling agent and binder, and 0.85 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - 750 g of this dispersion is mixed with 20 g of Li-carboxymethylcellulose powder and 968.5 g of the active ingredient LiFePO 4 (step C1 in which additional binder is introduced); - adding 20 g of an aqueous styrene-butadiene rubber latex suspension with a dry matter content of 50% by weight (additional binder addition step carried out before step (C2)); - Stir for 16 hours to produce a homogenous slurry (Step C2).

[0134] Due to both the single-walled carbon nanotubes and the gelling agent in the dispersion used to prepare the slurry, the resulting cathode slurry has a sharp and significant dependence of viscosity on shear rate, which is represented by a flow behavior index of 0.18 and a flow consistency index of 19.9 Pa s 0.18 This is well described by a power law with -1 At a shear rate of 1s, the dynamic viscosity is about 0.46 Pa s, which provides process capacity for application to the current collector plate. -1 At the following shear rates, the viscosity is at least 19.9 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0135] The storage stability of the slurry was determined by the method described in Example 1. For the cathode slurry of this example, the water content in the initial slurry was 42.3 wt.%, and after one week of storage, the water content was 43.0 wt.% in the upper third, 42.5 wt.% in the middle, and 41.5 wt.% in the lower third. The difference from the initial content of the solvent did not exceed 2 rel.%. The slurry can be used to fabricate cathodes after seven days of storage.

[0136] The resulting cathode slurry was used to produce a lithium ion battery cathode in the same manner as in Example 1. The initial specific capacity of the cathode material at a discharge current of 0.15 A / g was 147 mA·h / g of the cathode material.

[0137] The dispersion is used to prepare an anode slurry and an anode.

[0138] The dispersion was used to prepare an anode slurry containing 18 wt.% graphite active material, 32.9 wt.% silicon oxide active material, 44.6 wt.% water solvent, 3.1 wt.% carboxymethyl cellulose Li salt gelling agent and binder, 0.6 wt.% styrene butadiene rubber binder, and 0.9 wt.% single-walled carbon nanotubes. The anode slurry was prepared by the following sequence of steps: 37.5 g of the dispersion, 2.5 g of carboxymethylcellulose Li salt powder, 15 g of graphite powder and 27.4 g of silicon powder are mixed and stirred for 1 hour (stage (C1) in which additional binder is introduced). - adding 1 g of an aqueous styrene-butadiene rubber latex suspension with a dry matter content of 50% by weight (additional step of adding binder and water carried out before step (A2)); - Stir for 10 hours to produce a homogenous slurry (Step A2).

[0139] Due to the presence of both SWNTs and gelling agent, the resulting anode slurry also has a steep and significant dependence of viscosity on shear rate, which is described by a power law: the flow behavior index is 0.17 and the flow consistency index is 20.4 Pa s 0.17 It is. -1 At a shear rate of 1s, the slurry viscosity is less than 0.45 Pa·s, which provides process capacity for application to the current collector plate. -1 At shear rates below 100° C., the viscosity exceeds 20.4 Pa·s, which ensures the stability of the slurry during storage before use and the stability of the slurry layer on the current collector before drying.

[0140] The storage stability of the anode slurry was tested by the method described above in Example 1. Within one week, the water content in the top third of the slurry increased from 44.6 wt.% to 45.2 wt.% (i.e., 2 rel.% less than the initial value), indicating high slurry stability.

[0141] For the manufacture of the anode, the resulting anode slurry was applied to a copper foil using a doctor blade, dried for 1 hour at a temperature of 100°C and calendered at a force of 5 tons at 1.6 g / cm 3 The anode material density was 5.5 mg / cm. 2 The anode characteristics were measured using a cell with a Li cathode and a Li reference electrode, and LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 The initial specific capacity of the anode at a charging current of 0.1 A / g of the anode material is 900 mA·h / g of the anode material.

[0142] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 1.5 M solution of 1,200 mA·h was added to the electrolyte. The initial battery capacity was 1200 mA·h at a discharge rate of 0.1 C. The capacity as a function of the number of charge-discharge cycles (charge current 1200 mA, discharge current 1200 mA), referred to as the initial capacity, is shown in Figure 9. The battery capacity exceeds 96% of the initial capacity after 800 cycles. Example 6

[0143] The dispersion contains 2 wt. % of carboxymethylcellulose Na salt gelling agent and 0.3 wt. % of single-walled carbon nanotubes and their aggregates in water. The single-walled carbon nanotubes used to prepare the dispersion are Tuball™-99 SWCNTs. The diameter of the SWCNTs ranges from 1.2 to 2.1 nm, with an average diameter of 1.58 nm (the diameter was determined by TEM of the dried suspension and the absorption band S in the optical absorption spectrum of the suspension). 1-1Raman spectroscopy at 532 nm revealed a peak at 1580 cm typical of single-walled carbon nanotubes. -1 Strong G lines at around 1330 cm and other allotropic forms of carbon and defects in single-walled carbon nanotubes. -1 The G / D line intensity ratio is 56. The specific surface area determined from the nitrogen adsorption isotherm is 1160 m 2 / g. Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) shows that the SWCNTs contain 0.4 wt% iron (a metal in group 8 of the periodic table) impurity. The weight ratio of SWCNTs to HNBR in the slurry is 0.15.

[0144] Dispersions were prepared by mixing the required proportions of water, carboxymethylcellulose Na salt and SWCNTs and dispersing six-fold in a NETZSCH Omega 500 high-pressure homogenizer through a nozzle with a diameter of 700 μm at a pressure of 65 MPa and a dispersion transfer rate of 300 kg / h. The shear rate in the nozzle was approximately 6·10 5 s -1 The power consumption was 9 kW, and the specific input energy in stage (D) was about 30 W·h / kg. Between each of the two dispersion stages, the dispersion was placed in a 100 L tank and stirred for about 3 s by a gate agitator. -1 The mixture was stirred slowly for 20 minutes at a shear rate of 100 rpm.

[0145] The viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity as a function of shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.13 and the flow consistency index is 20.5 Pa s 0.13 1 / 6.3s -1 The dispersion viscosity in the low shear rate region is greater than 100 Pa s and is 18.6 s -1 In the region of shear rates above 1.6 Pa s, the shear strength is less than 1.6 Pa s.

[0146] The rheological properties of the dispersions were measured with a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 2800 Pa and the loss modulus G'' = 320 Pa, meaning that the dispersion is a highly viscous gel.

[0147] Using the dispersion, 66.1 wt. % of the active material LiNi 0.6 Co 0.2 Mn 0.2 O 2 A cathode slurry was prepared containing (NCM622), 30.3 wt% N-methylpyrrolidone (NMP) solvent, 2.2 wt% water, 1.32 wt% PVDF binder, 0.046 wt% carboxymethylcellulose Na salt gelling agent, and 0.0069 wt% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - 110 g of N-methylpyrrolidone and 4.8 g of polyvinylidene fluoride (PVDF) powder are added to 8.3 g of the dispersion and mixed for 30 minutes on an overhead stirrer (an additional step to introduce additional solvent (NMP) and binder before step (C2)). - mixing the mixture obtained with 240 g of active ingredient NCM622 (step (C1)); - Stir for 16 hours to produce a homogenous slurry (step (C2)).

[0148] Due to both the single-walled carbon nanotubes and the gelling agent in the dispersion used to prepare the slurry, the resulting cathode slurry has a sharp and significant dependence of viscosity on shear rate, which is represented by a flow behavior index of 0.28 and a flow consistency index of 22 Pa s 0.28This is well described by a power law with -1 At a shear rate of 1s, the dynamic viscosity is about 0.80 Pa s, which provides process capacity for application to the current collector plate. -1 At the following shear rates, the viscosity is at least 22 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0149] The storage stability of the slurry was determined by the method described in Example 1. The solvent (water and NMP) content in the initial slurry was 32.5 wt.%, and after one week of storage, the water content was 32.8 wt.% in the upper third, 32.7 wt.% in the middle, and 32.1 wt.% in the lower third. The difference from the initial content of solvent did not exceed 2 rel.%. The slurry can be used to fabricate cathodes after 7 days of storage.

[0150] The lithium-ion battery cathode was prepared by applying the resulting slurry to an aluminum foil current collector, drying the applied slurry until a cathode was formed, and calendering the cathode at a force of 5 tons to a density of 3.7 mg / cm. 2 The cathode properties were evaluated by compressing the Li cathode and Li reference electrode in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 The initial specific capacity of the cathode at a discharge current of 0.017 A / g of the cathode material is 173 mA·h / g of the cathode material.

[0151] The dispersion was used to prepare a 39% by weight graphite active material, 4.5% by weight silicon oxide SiO xAn anode slurry was prepared containing the active material, 55.1 wt.% water solvent, 1.35 wt.% carboxymethylcellulose Na salt (Na-CMC) gelling agent and binder, and 0.027 wt.% single-walled carbon nanotubes. The anode slurry was prepared in the following steps: 11.7 g of dispersion, 50 g of water, 1.27 g of Na-CMC powder, 43.5 g of graphite powder, and SiO x The slurry was prepared by mixing 5 g of silicon oxide powder (step (A1) in which additional water solvent and Na-CMC binder were introduced) and stirring for 12 hours to prepare a homogenous slurry (step (A2)).

[0152] Due to the presence of both SWNTs and gelling agent, the resulting anode slurry has a steep and significant dependence of viscosity on shear rate, which can be described by a power law: the flow behavior index is 0.25 and the flow consistency index is 11.6 Pa s 0.25 It is. -1 At a shear rate of 1s, the slurry viscosity is less than 0.37 Pa·s, which provides process capacity for application to the current collector plate. -1 At shear rates below 100° C., the viscosity exceeds 11.6 Pa·s, which ensures the stability of the slurry during storage before use and the stability of the slurry layer on the current collector before drying.

[0153] The storage stability of the anode slurry was tested by the method described above in Example 1. Within one week, the water content in the top third of the slurry increased from 55 wt.% to 55.6 wt.% (i.e., 2 rel.% less than the initial value), indicating high slurry stability.

[0154] For the manufacture of the anode, the resulting anode slurry was applied to a copper foil using a doctor blade, dried at a temperature of 100°C for 1 hour and calendered at a force of 5 tons at 1.5 g / cm 3 The anode properties were evaluated by measuring the density of the anode material in a cell with a Li cathode and Li reference electrode and LiPF in a 1:1:1 volumetric mixture of propylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents.6 The initial specific capacity of the anode at a charging current of 0.1 A / g of the anode material is 420 mA·h / g of the anode material.

[0155] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of ethylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 1.5 M solution of 20% v / v fluoroethylene carbonate was added and used as the electrolyte. The initial battery capacity was 2400 mA·h at a discharge rate of 0.1 C. The battery capacity after 500 charge-discharge cycles was more than 85% of the initial capacity (charge current 800 mA, discharge current 800 mA). Example 7

[0156] The dispersion contains 0.8 wt% carboxymethylcellulose Na salt gelling agent and 0.8 wt% single-walled carbon nanotubes and their aggregates in water. The dispersion was made using chlorine-modified Tuball™ SWCNTs as described in Example 1. The weight ratio of single-walled carbon nanotubes to gelling agent in the slurry is 1.

[0157] The dispersions were prepared by mixing the required proportions of water, Na-salt of polyacrylic acid, and SWCNTs, dispersing in a rotary pulsating apparatus (RPA) with a power consumption of 32 kW, rotor diameter of 190 mm, gap between rotor and stator of 700 μm, and rotor speed of 2940 rpm, sonicating in a 100 L tank at a frequency of 40 kHz and an acoustic input power of 1600 W sonotrode, and stirring in a 65 L tank at 30 rpm and approximately 2 s by an anchor stirrer. -1The dispersion was prepared by repeating 15 alternating stages of slow stirring and settling at a shear rate of 1 s. The rate of dispersion circulation between the RPA, the probe sonicator, and the tank was 1200 kg / h; about 25 W h / kg of energy was applied to the dispersion in the RPA in the dispersion stage (D); about 1.3 W h / kg was applied to the dispersion in the ultrasonic treatment stage (D); and about 1 s. -1 The average tank residence time of the dispersion at a shear rate of about 1.25 minutes in stage (R).

[0158] Dispersions were prepared by mixing the required proportions of water, carboxymethylcellulose Na salt and SWCNTs and dispersing six-fold in a NETZSCH Omega 500 high-pressure homogenizer through a nozzle with a diameter of 700 μm at a pressure of 65 MPa and a dispersion transfer rate of 300 kg / h. The shear rate in the nozzle was approximately 6·10 5 s -1 The power consumption was 9 kW, and the specific input energy in stage (D) was about 30 W·h / kg. Between each of the two dispersion stages, the dispersion was placed in a 100 L tank and stirred for about 3 s by a gate agitator. -1 The mixture was stirred slowly for 20 minutes at a shear rate of 100 rpm.

[0159] The viscosity was measured at a constant temperature of 25°C using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity as a function of shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.26 and the flow consistency index is 12.8 Pa s 0.26 1 / 6.3s -1 The dispersion viscosity in the low shear rate region is greater than 50 Pa s and is less than 18.6 s -1 In the region of shear rates above 1.5 Pa s, the shear strength is less than 1.5 Pa s.

[0160] The rheological properties of the dispersions were measured with a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d = 20 mm) using a spatula and thermostated at (T = 19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. For a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 905 Pa and the loss modulus G'' = 240 Pa, meaning that the dispersion is a highly viscous gel.

[0161] The dispersion was used to prepare a cathode active material of 49.6 wt.% LiFePO 4 A cathode slurry was prepared containing (LFP), 48.3 wt.% water solvent, 1 wt.% acetylene black, 1 wt.% Na-carboxymethylcellulose gelling agent and binder, and 0.014 wt.% single-walled carbon nanotubes. The cathode slurry was prepared by the following sequence of steps: - 1.7 g of the dispersion, 45 g of water, 1 g of Na-carboxymethylcellulose powder, 1 g of acetylene black and 48 g of the active ingredient LFP are mixed (stage C1 in which water, conductive additives and binders are also introduced). - Stir for 16 hours to produce a homogenous slurry (Step C2).

[0162] Due to both the single-walled and double-walled carbon nanotubes in the dispersion and the gelling agent used to prepare the slurry, the resulting cathode slurry has a sharply significant dependence of viscosity on shear rate, which is well described by a power law. The flow behavior index is 0.27 and the flow consistency index is 14.4 Pa s 0.27 93s -1 The viscosity measured at a shear rate of 100 s was 0.51 Pa s. -1 Extrapolation of the shear rate dependence of gives a viscosity estimate of about 0.50 Pa s, which provides a process capacity for application to the current collector plate. -1At the following shear rates, the viscosity is at least 14.4 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0163] The storage stability of the cathode slurry was tested by the method described above in Example 1. Within one week, the water content of the top third of the slurry increased from 48.3 wt.% to 49.0 wt.% (i.e., 2 rel.% less than the initial value), indicating high slurry stability.

[0164] The dispersion was used to prepare an anode slurry containing 45.9 wt. % graphite active material, 53.1 wt. % water solvent, 0.93 wt. % Na-carboxymethylcellulose gelling agent, and 0.13 wt. % single-walled carbon nanotubes. The anode slurry was prepared by the following sequence: mixing 1.7 g of the dispersion, 55 g of water, 0.98 g of Na-CMC powder, and 49 g of graphite powder (Step A1), and stirring the resulting mixture for 12 hours to prepare a homogenous slurry (Step A2).

[0165] Due to both the single-walled and double-walled carbon nanotubes in the dispersion and the gelling agent used to prepare the slurry, the resulting anode slurry has a sharply significant dependence of viscosity on shear rate, which is well described by a power law: the flow behavior index is 0.22 and the flow consistency index is 12.8 Pa s 0.22 93s -1 The viscosity measured at a shear rate of 100 s was 0.37 Pa s. -1 Extrapolation of the shear rate dependence of gives a viscosity estimate of about 0.35 Pa s, which provides a process capacity for application to the current collector plate. -1 At the following shear rates, the viscosity is at least 12.8 Pa·s, which ensures slurry stability during storage before use and the stability of the slurry layer on the current collector before drying.

[0166] The storage stability of the anode slurry was tested by the method described above in Example 1. Within one week, the water content of the top third of the slurry increased from 53.6 wt.% to 54.7 wt.% (i.e., 2 rel.% less than the initial value), indicating high slurry stability.

[0167] For the manufacture of the anode, the resulting anode slurry was applied to a copper foil using a doctor blade, dried for 1 hour at a temperature of 100°C and calendered at a force of 5 tons at 1.7 g / cm 3 The anode properties were evaluated by measuring the density of the anode material in a cell with a Li cathode and Li reference electrode, and LiPF in a 1:1:1 volumetric mixture of ethylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 The initial specific capacity of the anode material at a charging current of 0.1 A / g was determined by assembling an electrolyte containing a 1 M solution of 10% v / v fluoroethylene carbonate and an additional 10% v / v fluoroethylene carbonate. . h / g.

[0168] A lithium ion battery was assembled from the resulting cathode and anode. A polypropylene separator with a thickness of 16 μm was used. LiPF in a 1:1:1 volumetric mixture of ethylene carbonate:ethyl methyl carbonate:dimethyl carbonate solvents. 6 A 1.5 M solution of 20% v / v fluoroethylene carbonate was added and used as the electrolyte. The initial battery capacity was 1250 mA·h at a discharge rate of 0.1 C. The battery capacity was 1130 mA·h after 1000 cycles, i.e., more than 90% of the initial capacity. Example 8 (comparative example).

[0169] The dispersion contains 0.4 wt. % SWCNTs as described in Example 1, and water. The dispersion does not contain a gelling agent. The dispersion was prepared as in Example 1.

[0170] The dispersion viscosity was measured at a constant temperature of 25° C. using a Brookfield DV2-TLV viscometer equipped with an SC4-21 spindle. The viscosity as a function of shear rate was 0.093 s -1 ~100s -1 The flow behavior index n is 0.62 and the flow consistency index is 3.0 Pa s 0.62 1 / 6.3s -1 The dispersion viscosity in the low shear rate region below 18.6 s is approximately 6 Pa s. -1 At shear rates above 1 Pa·s, the dispersion viscosity is about 1 Pa·s. At low shear rates, the dispersion viscosity is below 20 Pa·s, which is not sufficient to ensure dispersion stability during long-term storage.

[0171] The rheological properties of the dispersions were measured using a HAAKE RheoStress 6000 dynamic shear rheometer in an interplate cell with a gap of 0.5 mm. The dispersion sample was transferred to the lower plate (d=20 mm) using a spatula and thermostated at (T=19-21 °C), then the plates were closed to a gap of 0.55 mm, after which the excess sample was removed using a metal spatula and the plates were closed again to a measuring gap of 0.5 mm. At a deformation amplitude of 1%, corresponding to a rotation angle of 0.029° of the moving plate, the storage modulus G' was 103 Pa and the loss modulus G''=19 Pa, which also indicates a rather low viscosity of the obtained gel.

[0172] The dispersion was used to prepare a cathode slurry with the same composition and preparation sequence as in Example 1, except that no gelling agent was present in the dispersion. Accordingly, a corresponding amount of gelling agent was added in the form of a Na-carboxymethylcellulose solution: - 54 g of a solution containing 1 g of Na-carboxymethylcellulose and 53 g of water are added to 12.5 g of the dispersion prepared and mixed on an overhead stirrer for 30 minutes. - The resulting mixture was mixed with 97.75 g of the active ingredient LiFePO 4 Mix with; -Add 2.4 g of aqueous styrene butadiene rubber latex with a dry matter content of 50%; - Stir for 16 hours to produce a homogenous slurry.

[0173] The viscosity of the resulting cathode slurry as a function of shear rate is shown by the dark boxes (curve 8C) in Figure 3. This dependence is consistent with a flow behavior index of n = 0.46 and a flow consistency index of 9.3 Pa s 0.46 The viscosity of the slurry is described by the Ostwald-de Waele power law with -1 This viscosity is not sufficient to achieve the required technical results that there is no delamination of the cathode slurry during storage and that the cathodes obtained by applying the slurry to a current collector are of high quality, as shown by slurry storage stability studies and cathode application experiments.

[0174] The storage stability of the slurries was determined by changing the distribution of the solid particle content along the height of the slurry layer after storage of the slurries in 50 ml cylindrical test tubes with a diameter of 30 mm. For this purpose, the slurries were placed in test tubes, closed with lids, kept under standard conditions (atmospheric pressure, 25°C) for 7 days, and analyzed similarly to the procedure described in Example 1. A turbid supernatant layer of about 6 mm thickness formed on the surface of the slurry in 7 days. For the cathode slurry of this example, the solvent content in the initial slurry was 40 wt.%, and after 1 week of storage, the solvent content was 54.1 wt.% in the upper third, 36.5 wt.% in the middle, and 29.6 wt.% in the lower part. There was significant delamination of the cathode slurry, which prevented application after 7 days.

[0175] If one were to use the resulting cathode slurry to manufacture a cathode, it would be impossible to obtain a high-quality coating of the current collector with the cathode slurry (see FIG. 4 (right photo)). The resulting dispersion without gelling agent, and the cathode slurry manufactured with this dispersion, would not be able to obtain the required technical result.

[0176] The dispersion was used to prepare an anode slurry with the same composition and preparation sequence as in Example 1, except that no gelling agent was present in the dispersion. Therefore, a corresponding amount of gelling agent was added in the form of a Na-carboxymethylcellulose solution. The anode slurry was prepared by the following sequence of steps: - Mix 187.5 g of the dispersion, 1388 g of water, 112 g of a 1 wt. % Na-CMC aqueous solution, 1000 g of graphite powder, and 454.2 g of silicon powder and stir for 10 hours; - adding 54 g of a 50% by weight aqueous butadiene styrene latex suspension; - Stir for 2 hours to produce a homogenous slurry.

[0177] The storage stability of the slurry was determined by the same procedure as described in Example 1. A cloudy supernatant layer about 8 mm thick formed on the surface of the slurry in 7 days. For the anode slurry of this example, the solvent content in the initial slurry was 53.6 wt %, and after one week of storage, the solvent content was 68.1 wt % in the top third, 48.0 wt % in the middle, and 44.2 wt % in the bottom. There was significant delamination of the cathode slurry, preventing coating after 7 days.

[0178] Table 1 below summarizes the compositions and properties of the dispersions of Examples 1-8.

[0179] Table 2 below summarizes the compositions and properties of the cathode and anode slurries of Examples 1-8. [Table 1] [Table 2] [Industrial Applicability]

[0180] The present invention, in one embodiment, is used to produce dispersions of single-walled and / or double-walled carbon nanotubes in a liquid phase and agglomerates thereof, electrode slurries, lithium ion battery electrodes, and lithium ion batteries.

[0181] It should also be understood that various modifications, adaptations, and alternative embodiments thereof can be made within the scope and spirit of the present invention. The present invention is further defined by the following claims.

Claims

1. - water, - gelling agents, as well as - a dispersion comprising single-walled and / or double-walled carbon nanotubes, The content of the single-walled and / or double-walled carbon nanotubes is in the range of 0.3 to 2% by weight, wherein the weight ratio of the single-walled and / or double-walled carbon nanotubes to the gelling agent is at least 0.05 and not more than 10; A dispersion comprising gel particles formed by aggregates of molecules of the gelling agent physically bound into a weak gel network by the single-walled carbon nanotubes and / or double-walled carbon nanotubes.

2. The dispersion has a flow behavior index "n" of 0.37 or less and a viscosity of at least 3.2 Pa.s n 2. The dispersion of claim 1, which is a pseudoplastic power law fluid having a flow consistency index "K" of

3. 2. The dispersion of claim 1, wherein the dispersion has a loss modulus of at least 27 Pa when subjected to oscillatory shear strain at a frequency of 1 Hz and a relative shear strain amplitude of 1%.

4. 2. The dispersion of claim 1, wherein the gelling agent is any one of carboxymethylcellulose or a salt of carboxymethylcellulose, polyvinylpyrrolidone, polyacrylic acid or a salt of polyacrylic acid, or mixtures thereof.

5. 10. The dispersion of claim 1, wherein the single-walled and / or double-walled carbon nanotubes contain at least 0.1 wt. % of functional groups on their surfaces.

6. The dispersion of claim 5, wherein the single-walled and / or double-walled carbon nanotubes contain at least 0.1% by weight of chlorine and / or at least 0.1% by weight of carbonyl groups and / or hydroxyl groups and / or carboxyl groups on their surfaces.

7. 2. The dispersion of claim 1, wherein the ratio of G / D line intensities in a Raman spectrum of the single-walled and / or double-walled carbon nanotubes at a wavelength of 532 nm is at least 10.

8. The dispersion of claim 1, wherein the single-walled and / or double-walled carbon nanotubes and / or aggregates thereof contain metal impurities from Groups 8 to 11.

9. 9. The dispersion of claim 8, wherein the single-walled and / or double-walled carbon nanotubes and / or aggregates thereof contain less than 1 wt. % of Group 8 to Group 11 metal impurities.

10. The dispersion of claim 1, wherein the flow behavior index "n" and the flow consistency index "K" of the dispersion satisfy the condition n<1.25.lg(K / (Pa.s n ))-0.628 and / or n<1.24-0.787.lg(K / (Pa.s n )).

11. A method for producing a dispersion, comprising a series of at least three dispersion steps (D) and at least two alternating resting steps (R), wherein any of the dispersion steps (D) comprises: (i) a dispersion time of at least 10,000 s -1 or (ii) mechanically processing the dispersion at a shear rate of at least 10 Hz and a specific input energy of at least 10 W-h / kg; or (ii) sonicating the dispersion at a frequency of at least 20 kHz and a specific input energy of at least 1 W-h / kg; The resting step (R) comprises resting the dispersion between two successive dispersion steps (D) for at least 1 minute, 10 s -1 and exposing the material to a shear rate of less than Thereby producing the dispersion containing water, a gelling agent, and 0.3-2 wt. % single-walled and / or double-walled carbon nanotubes, wherein the weight ratio of the single-walled and / or double-walled carbon nanotubes to the gelling agent is at least 0.05 and no more than 10.

12. 12. The method of claim 11, comprising a series of at least 10 dispersion steps (D) and at least 9 alternating rest steps (R).

13. The series of dispersion steps (D) and alternating resting steps (R) comprises: (i) one or several devices providing the mechanical processing or the ultrasonic treatment; (ii) a device in which the dispersion is held for 10 s; -1 12. The method of claim 11, comprising circulating the dispersion between a slowly stirred tank at a shear rate of less than 100 rpm.

14. The method of claim 13 , wherein the dispersion circularity factor is at least 10.

15. The method comprises: (i) performing a process for 10,000 s with a specific input energy of greater than 10 W h / kg; -1 and (ii) a ultrasonic treatment device having a rotary pulsating device at a shear rate of more than 10 s, a half wave or wave activation device immersed in the dispersion at a frequency of at least 20 kHz and a specific input energy of more than 1 W h / kg; and (iii) a method for treating the dispersion in a manner such that the dispersion is held for more than 1 minute on average and is heated to 10 s. -1 14. The method of claim 13, comprising circulating the dispersion between a slowly stirred tank at a shear rate of less than 100 to 10,000 kg / h.

16. The method comprises: (i) performing a -1 and a specific input energy of at least 10 W·h / kg; and (ii) the dispersion is held for an average of at least 1 minute for 10 s -1 14. The method of claim 13, comprising circulating the dispersion between a slowly stirred tank at a shear rate of less than 100 to 10,000 kg / h.

17. A method for producing a cathode slurry, comprising the steps of: mixing (C1) the cathode active material and the dispersion; and A step of stirring (C2) the obtained mixture to produce a uniform slurry; Including, The method, wherein the dispersion comprises a cathode active material, water, a gelling agent, and at least 0.005 wt. % single-walled and / or double-walled carbon nanotubes.

18. The method further comprises adding, during the mixing step (C1), the water and / or the water-soluble organic solvent and / or one or several binders and / or conductive additives; and / or 18. The method according to claim 17, further comprising one or several steps of mixing with water and / or a water-soluble organic solvent and / or one or several binders and / or conductive additives prior to the stirring step (C2).

19. The process of claim 18, (A1) mixing an active anode material with a dispersion; the anode active material comprises a graphite phase, a silicon phase, a silicon oxide (SiO x ) phase (x is an integer less than or equal to 2), or a combination of a silicon phase and a silicon oxide (SiO x ) phase, where the total atomic ratio between oxygen and silicon in the anode active material is greater than 0 and less than 1.8, and the dispersion comprises a cathode active material, water, a gelling agent, and at least 0.01 wt. of single-walled and / or double-walled carbon nanotubes; and (A2) A step of stirring the resulting mixture to produce a uniform slurry. The method for producing an anode slurry comprising the steps of:

20. 20. The method according to claim 19, wherein water and / or a water-soluble organic solvent and / or one or several binders and / or conductive additives are added to the mixture during the mixing step (A1) and / or the method further comprises one or several preliminary steps (A0) of mixing with water and / or a water-soluble organic solvent and / or one or several binders and / or conductive additives, the one or several preliminary steps (A0) being carried out before the stirring step (A2).